Multilayer film having at least three layers and method for producing same - Patents.com
Patent Information
- Application Number
- JP2022503809
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-08-06
- Filing Date
- 2020-08-04
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2040-08-04
AI Technical Summary
Conventional multilayer films with a polyamide core layer face challenges such as increased process complexity, non-recyclability, and higher material costs, while attempts to improve modulus or dart resistance often result in trade-offs like loss of toughness or increased thickness, making it difficult to achieve a balance of properties like dirt/bag drop resistance, puncture resistance, and creep resistance.
A multilayer film structure comprising at least three layers, including a polyethylene composition core layer with specific elution profile characteristics, such as a single peak in temperature ranges of 45°C to 87°C and 95°C to 120°C, and a ratio of these peaks' areas, which provides improved toughness and creep resistance without a polyamide core, allowing for reduced thickness and simplified production.
The multilayer film achieves enhanced dart strength, puncture resistance, and creep resistance at reduced thickness, maintaining desired physical properties while reducing material costs and complexity, enabling more efficient production and recyclability.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical Field]
[0001] Cross-reference of related applications This application claims priority to U.S. Provisional Patent Application No. 62 / 883,469, filed on August 6, 2019, and U.S. Provisional Patent Application No. 62 / 883,467, filed on August 6, 2019, the entire disclosure thereof being incorporated herein by reference.
[0002] The embodiments described herein generally relate to multilayer films, and more specifically to multilayer films containing polyethylene. [Background technology]
[0003] Improving sustainability is a goal for manufacturers of multilayer films, including polyethylene. Therefore, it is beneficial that single-layer and multilayer polymer films, which may include inflation or cast films, exhibit toughness while enabling reductions in material costs, for example, by down-gauge (i.e., using thinner film thicknesses) or by reducing or eliminating relatively expensive materials such as polyamides. [Overview of the Initiative]
[0004] In conventional multilayer films, a desirable balance between the dirt coefficient and the film coefficient can be achieved by including a polyamide core layer in the multilayer film structure. However, the incorporation of a polyamide core layer increases process complexity, increases the complexity of the film structure, can produce unreusable multilayer films, and can increase material costs. However, typically, without the incorporation of a polyamide core layer, attempts to improve the coefficient through film modification can result in a loss of dirt, and attempts to improve dirt typically result in a loss of coefficient. Furthermore, obtaining a polymer film with sufficient toughness while enabling material cost reduction through downgauge is often difficult.
[0005] Therefore, there is a need for multilayer films that exhibit physical properties such as dirt / bag drop resistance, puncture resistance, tear resistance, and creep resistance, meeting customer and industry requirements. In some embodiments, these multilayer films can still maintain physical properties that meet customer and industry requirements even with reduced thickness or without a polyamide core layer.
[0006] Embodiments of the present disclosure satisfy the need by providing multilayer films comprising at least three layers that provide a balance of rigidity and abuse properties (e.g., dig, puncture energy, tear) in various embodiments. Such multilayer films may include a polyethylene composition in the core layer that exhibits an improved balance of toughness and creep resistance. Furthermore, when the overall thickness of a multilayer containing a polyethylene composition in the core layer is reduced, this multilayer film may still exhibit an improved balance of toughness and creep resistance compared to conventional multilayer films.
[0007] According to at least one embodiment, a multilayer film is provided. Embodiments of the multilayer film may include a first layer comprising a polyethylene composition, a second layer comprising a first polyolefin, and a third layer comprising a second polyolefin. The first layer may be placed between the second and third layers. The first and second polyolefins may have the same or different compositions. The polyethylene composition may include (a) a first polyethylene fraction having a single peak in the temperature range of 45°C to 87°C in the elution profile obtained by an improved comonomer composition distribution (iCCD) analysis, wherein the area of the first polyethylene fraction is the area in the elution profile below the single peak of the first polyethylene fraction at 45°C to 87°C; and (b) a second polyethylene fraction having a single peak in the temperature range of 95°C to 120°C in the elution profile obtained by an iCCD analysis, wherein the area of the second polyethylene fraction is the area in the elution profile below the single peak of the second polyethylene fraction at 95°C to 120°C, and the polyethylene composition may contain 0.924 g / cm³ 3 ~0.936 g / cm³ 3 It has a density and a melt index (I2) of 0.25 g / 10 min to 2.0 g / 10 min, the area of the first polyethylene fraction constitutes at least 40% of the total area of the elution profile, the ratio of the area of the first polyethylene fraction to the area of the second polyethylene fraction is 0.75 to 2.5, and the width of the single peak of the second polyethylene fraction at 50 percent of the peak height is less than 5.0°C.
[0008] According to at least one more embodiment, a multilayer film is provided. An embodiment of the multilayer film is a first layer, 0.910~0.936 g / cm² 3 A second layer containing a first linear low-density polyethylene having a density of 0.910~0.936 g / cm³ 3The first and second linear low-density polyethylenes may comprise a third layer comprising a second linear low-density polyethylene having a density of 1.5. The first and second linear low-density polyethylenes may have the same or different compositions. The first layer may be placed between the second and third layers. The first layer may constitute 10% to 80% by weight of the total weight of the multilayer film. The first layer may comprise a polyethylene composition. The polyethylene composition may include (a) a first polyethylene fraction having a single peak in the temperature range of 45°C to 87°C in the elution profile by an improved comonomer composition distribution (iCCD) analysis, wherein the area of the first polyethylene fraction is the area within the elution profile below the single peak of the first polyethylene fraction at 45°C to 87°C; and (b) a second polyethylene fraction having a single peak in the temperature range of 95°C to 120°C in the elution profile by an iCCD analysis, wherein the area of the second polyethylene region is the area within the elution profile below the single peak of the second polyethylene fraction at 95°C to 120°C, and the polyethylene composition may contain 0.924 g / cm³ 3 ~0.936 g / cm³ 3 It has a density and a melt index (I2) of 0.25 g / 10 min to 2.0 g / 10 min, the area of the first polyethylene fraction constitutes at least 40% of the total area of the elution profile, the ratio of the area of the first polyethylene fraction to the area of the second polyethylene fraction is 0.75 to 2.5, and the width of the single peak of the second polyethylene fraction at 50 percent of the peak height is less than 5.0°C.
[0009] According to at least one more embodiment, a multilayer film is provided. Embodiments of the multilayer film may include a first layer, a second layer, and a third layer. The first layer may be placed between the second and third layers. The first layer has a density of 0.940 g / cm³ when measured according to ASTM 742. 3 ~0.970g / cm 3It may include a high-density polyethylene composition having a density of, and a polyethylene composition. The second layer may include at least 50 wt% of a first linear low-density polyethylene based on the total weight of the second layer, and the first linear low-density polyethylene has a density of 0.910 g / cm 3 ~0.936 g / cm 3 The third layer, which has a density of, may include at least 50 wt% of a second linear low-density polyethylene based on the total weight of the second layer, and the second linear low-density polyethylene has a density of 0.910 g / cm 3 ~0.936 g / cm 3 The first linear low-density polyethylene and the second linear low-density polyethylene may be the same or different in composition. The polyethylene composition may include (a) a first polyethylene fraction having a single peak in the temperature range of 45°C to 87°C in the elution profile by an improved comonomer composition distribution (iCCD) analysis method, wherein the area of the first polyethylene fraction is the area within the elution profile under the single peak of the first polyethylene fraction at 45°C to 87°C, and (b) a second polyethylene fraction having a single peak in the temperature range of 95°C to 120°C in the elution profile by the iCCD analysis method, wherein the area of the second polyethylene fraction is the area within the elution profile under the single peak of the second polyethylene fraction at 95°C to 120°C. This polyethylene composition has a density of 0.924 g / cm 3 ~0.936 g / cm 3 and a melt index (I2) of 0.25 g / 10 min to 2.0 g / 10 min. The area of the first polyethylene fraction constitutes at least 40% of the total area of the elution profile, the ratio of the area of the first polyethylene fraction to the area of the second polyethylene fraction is 0.75 to 2.5, and the width of the single peak of the second polyethylene fraction at 50% of the peak height is less than 5.0°C.
[0010] According to at least one more embodiment, a multilayer film is provided. Embodiments of the multilayer film may include a first layer, a second layer, and a third layer. The first layer may be placed between the second and third layers. The first layer has a density of 0.940 g / cm³. 3 ~0.970g / cm 3 First polyethylene having a density of 0.924 g / cm³ 3 ~0.936 g / cm³ 3 The second layer may contain a first polyethylene composition having a density of 0.940 g / cm³. 3 ~0.970g / cm 3 A second polyethylene having a density of 0.916 g / cm³ 3 ~0.935g / cm 3 A first low-density polyethylene composition having a density of , and 0.924 g / cm³ 3 ~0.936 g / cm³ 3 The third layer may contain a second polyethylene composition having a density of 0.916 g / cm³. 3 ~0.935g / cm 3 A second low-density polyethylene composition having a density of 0.924 g / cm³ 3 ~0.936 g / cm³ 3It may include a third polyethylene composition having a density of . The first polyethylene and the second polyethylene may have the same or different compositions. The first low-density polyethylene and the second low-density polyethylene may have the same or different compositions. The first polyethylene composition, the second polyethylene composition, and the third polyethylene composition may be the same or different compositions, each comprising: (a) a first polyethylene fraction having a single peak in the temperature range of 45°C to 87°C in an improved comonomer composition distribution (iCCD) analysis elution profile, wherein the area of the first polyethylene fraction is the area in the elution profile below the single peak of the first polyethylene fraction at 45°C to 87°C; and (b) a second polyethylene fraction having a single peak in the temperature range of 95°C to 120°C in an iCCD analysis elution profile, wherein the area of the second polyethylene fraction is the area in the elution profile below the single peak of the second polyethylene fraction at 95°C to 120°C; and the polyethylene composition may comprise 0.924 g / cm³ 3 ~0.936 g / cm³ 3 It has a density and a melt index (I2) of 0.25 g / 10 min to 2.0 g / 10 min, the area of the first polyethylene fraction constitutes at least 40% of the total area of the elution profile, the ratio of the area of the first polyethylene fraction to the area of the second polyethylene fraction is 0.75 to 2.5, and the width of the single peak of the second polyethylene fraction at 50 percent of the peak height is less than 5.0°C.
[0011] These and other embodiments will be described in more detail in the embodiments for carrying out the invention described below, in conjunction with the accompanying drawings. [Brief explanation of the drawing]
[0012] The following detailed description of specific embodiments of this disclosure will be best understood in conjunction with the following drawings, in which similar structures are shown with similar reference numerals.
[0013] [Figure 1] The iCCD elution profiles of one or more embodiments described herein are schematically shown. [Figure 2] The iCCD elution profiles of the polyethylene composition of Example 1, according to one or more embodiments described herein, are shown graphically. [Figure 3] A schematic diagram of a reactor system useful for producing polyethylene, according to one or more embodiments described herein, is shown. [Figure 4] A schematic diagram illustrates another reactor system useful for producing polyethylene, based on one or more embodiments described herein. [Modes for carrying out the invention]
[0014] Herein, specific embodiments of this application will be described. These embodiments are provided so as to ensure that this disclosure is detailed and complete and to fully convey the scope of the claimed subject matter to those skilled in the art.
[0015] Unless otherwise stated, implied by the context, or customary in the art, all part and percentage values are based on weight, all temperatures are in degrees Celsius, and all test methods are current as of the filing date of this disclosure.
[0016] The term "polymer" refers to polymer compounds prepared by polymerizing monomers, whether of the same or different types. Therefore, the general term "polymer" typically includes the term "homopolymer," which refers to polymers prepared from only one type of monomer, and "copolymer," which refers to polymers prepared from two or more different monomers. As used herein, the term "interpolymer" refers to polymers prepared by polymerizing at least two different types of monomers. Thus, the general term "interpolymer" includes copolymers and polymers prepared from three or more different monomers, such as terpolymers.
[0017] "Polyethylene" or "ethylene polymer" means a polymer containing units derived from more than 50 mol% ethylene monomers. This includes ethylene homopolymers or copolymers (meaning units derived from two or more comonomers). Common forms of ethylene polymers known in the art include, but are not limited to, low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), ultra-low-density polyethylene (ULDPE), very low-density polyethylene (VLDPE), single-site catalyst linear low-density polyethylene (m-LLDPE), which includes both linear and substantially linear low-density resins, medium-density polyethylene (MDPE), and high-density polyethylene (HDPE).
[0018] As used herein, the term “composition” refers to a mixture of materials comprising a composition, as well as reaction products and decomposition products formed from the materials of the composition.
[0019] As used herein, the terms “polypropylene” or “propylene polymer” refer to polymers that consist of units derived from more than 50 mol% of propylene monomer in their polymerized form. This includes propylene homopolymers, random copolymer polypropylenes, impact copolymer polypropylenes, propylene / α-olefin copolymers, and propylene / α-olefin copolymers.
[0020] The term "LDPE" may also be referred to as "high-pressure ethylene polymer" or "highly branched polyethylene," and is defined to mean that the polymer is partially or completely homopolymerized or copolymerized in an autoclave or tubular reactor at a pressure exceeding 14,500 psi (100 MPa) using free radical initiators such as peroxides (see, for example, U.S. Patent No. 4,599,392 incorporated herein by reference). LDPE resins typically have a viscosity of 0.916 g / cm³. 3 ~0.940g / cm 3 It has a density within the range.
[0021] The term "LLDPE" includes resins prepared using the Ziegler-Natta catalyst system, as well as resins prepared using single-site catalysts, including but not limited to bismetallocene catalysts (sometimes referred to as "m-LLDPE"), phosphinimine, and constrained geometric catalysts, and resins prepared using post-metallocene molecular catalysts, including but not limited to bis(biphenylphenoxy) catalysts (also referred to as polyvalent aryloxy ether catalysts). LLDPEs include linear, substantially linear, or heterogeneous ethylene copolymers or homopolymers. LLDPE contains fewer long-chain branches than LDPE and includes substantially linear ethylene polymers as further defined in U.S. Patents 5,272,236, 5,278,272, 5,582,923 and 5,733,155; homogeneous branched linear ethylene polymer compositions such as those in U.S. Patent 3,645,992; heterogeneous branched ethylene polymers such as those prepared according to the process disclosed in U.S. Patent 4,076,698; and blends thereof (such as those disclosed in U.S. Patents 3,914,342 and 5,854,045). LLDPE resins can be produced by gas-phase, solution-phase, or slurry polymerization, or any combination thereof, using any type of reactor or reactor configuration known in the art.
[0022] The term "MDPE" refers to 0.924 g / cm³ 3 ~0.942 g / cm³ 3 This refers to polyethylene having a density of 1 / 2. "MDPE" is typically produced using chromium or Ziegler-Natta catalysts, or single-site catalysts including, but not limited to, substituted mono- or bis-cyclopentadienyl catalysts (typically referred to as metallocenes), bound geometric catalysts, phosphinimine catalysts, and polyvalent aryloxy ether catalysts (typically referred to as bisphenylphenoxy).
[0023] The term "HDPE" generally refers to single-site catalysts, including but not limited to Ziegler-Natta catalysts, chromium catalysts, or substituted mono- or bis-cyclopentadienyl catalysts (typically referred to as metallocenes), bound geometric catalysts, phosphiminine catalysts, and polyvalent aryloxy ether catalysts (typically referred to as bisphenylphenoxy), prepared at a concentration of approximately 0.935 g / cm³. 3 Super ~ maximum approx. 0.980g / cm 3 This refers to polyethylene having a certain density.
[0024] The term "ULDPE" generally refers to single-site catalysts, including but not limited to Ziegler-Natta catalysts, chromium catalysts, or substituted mono- or bis-cyclopentadienyl catalysts (typically referred to as metallocenes), bound geometric catalysts, phosphiminine catalysts, and polyvalent aryloxy ether catalysts (typically referred to as bisphenylphenoxy), prepared at a concentration of 0.855 g / cm³. 3 ~0.912 g / cm³ 3 This refers to polyethylene having a density of 0.855 g / cm³. ULDPE includes, but is not limited to, polyethylene (ethylene-based) plastomers and polyethylene (ethylene-based) elastomers. Polyethylene (ethylene-based) elastomer plastomers generally have a density of 0.855 g / cm³. 3 ~0.912 g / cm³ 3 It has a density of .
[0025] The terms “blend,” “polymer blend,” and similar terms mean a composition of two or more polymers. Such a blend may or may not be miscible. Such a blend may or may not be phase-separated. Such a blend may or may not contain one or more domain configurations, as determined by transmission electron spectroscopy, light scattering, X-ray scattering, and any other method known in the art. A blend is not a laminate, but one or more layers of a laminate may contain a blend. Such a blend may be formed as a dry blend, in situ (e.g., in a reactor), as a molten blend, or by other techniques known to those skilled in the art.
[0026] A "multilayer structure" or "multilayer film" means any structure having two or more layers. For example, a multilayer structure (e.g., a film) may have two, three, four, five, or more layers. A multilayer structure can be described as having layers specified by letters. For example, a three-layer structure designated A / B / C may have a core layer B, and two outer layers A and C. Similarly, a structure having two core layers B and C, and two outer layers A and D would be designated A / B / C / D.
[0027] The terms “comprising,” “including,” and “having,” and their derivatives, are not intended to exclude the existence of any additional components, processes, or procedures, whether or not they are specifically disclosed. To avoid any doubt, all compositions claimed through the use of the term “comprising” may include any additional additives, adjuvants, or compounds, whether polymeric or otherwise, unless otherwise stated. In contrast, the term “essentially consisting of” excludes any other components, processes, or procedures from the scope of any subsequent description, except those not essential to operability. The term “consisting of” excludes any components, processes, or procedures not specifically specified or listed.
[0028] Multilayer film Here, we refer to embodiments of multilayer films described herein. Embodiments of multilayer films described herein may include at least three layers.
[0029] The multilayer films of this disclosure may comprise at least three layers, and even thirteen or more layers. The number of layers in a multilayer film may depend on a number of factors, including, for example, the composition of each layer of the multilayer film, the desired properties of the multilayer film, the desired end use of the multilayer film, and the manufacturing process of the multilayer film. A multilayer film may be a three-layer structure designated as A / B / C, where the first layer may be designated as A, the second layer as B, and the third layer as C. In some embodiments, the first layer may be referred to as the “core layer.” In some embodiments, one or both of the second and third layers may be referred to as the “skin layer” or “outer layer.” In embodiments, the first layer may be located between the second and third layers. In further embodiments, the second and third layers may be the outermost layers of the multilayer film. As used herein, the outermost layer of a multilayer film may mean that there may be no other layer deposited on top of the outermost layer so that the outermost layer is in direct contact with the surrounding air.
[0030] In embodiments, the first layer and the second layer, the first layer and the third layer, or both, may be in direct contact with each other. As used herein, “direct contact” means that there may be no other layers positioned between two layers that are in direct contact with each other. In other embodiments, the multilayer film may include one or more additional layers, for example, one or more tie layers, which may be positioned between the first layer (core layer) and the second layer (outer layer), between the first layer (core layer) and the third layer (another outer layer), or both.
[0031] As will be described in more detail later in this disclosure, a multilayer film may comprise a first layer comprising a polyethylene composition, a second layer comprising a first polyolefin, and a third layer comprising a second polyolefin. The first and second polyolefins may have the same or different compositions. It should be understood that any of the aforementioned layers may further comprise one or more additives known to those skilled in the art, such as plasticizers, stabilizers including viscosity stabilizers, hydrolysis stabilizers, primary and secondary antioxidants, ultraviolet absorbers, antistatic agents, dyes, pigments or other colorants, inorganic fillers, flame retardants, lubricants, reinforcing agents such as glass fibers and flakes, synthetic (e.g., aramid) fibers or pulp, forming agents or foaming agents, processing aids, slip additives, anti-tack agents such as silica or talc, release agents, tackifying resins, or two or more combinations thereof. Inorganic fillers such as calcium carbonate and their analogues may also be incorporated into one or more of the first layer, the second layer, the third layer, and combinations thereof. In some embodiments, a first layer, a second layer, a third layer, and combinations may each contain up to 5 weight percent of such additional additives based on the total weight of each layer. All individual values and subranges from 0% to 5% by weight are included and disclosed herein, for example, the total amount of additives in the first layer, the second layer, or the third layer may be 0.5% to 5%, 0.5% to 4%, 0.5% to 3%, 0.5% to 2%, 0.5% to 1%, 1% to 5%, 1% to 4%, 1% to 3%, 1% to 2%, 2% to 5%, 2% to 4%, 2% to 3%, 3% to 5%, 3% to 4%, or 4% to 5% by weight, based on the total weight of each layer. The incorporation of additives can be carried out by any known process, such as dry blending, extrusion of a mixture of various components, or conventional masterbatch technology.
[0032] The multilayer film of the present invention can have various thicknesses. The thickness of the multilayer film can depend on a number of factors, including, for example, the number of layers in the multilayer film, the composition of the layers in the multilayer film, the desired properties of the multilayer film, the desired end use of the film, and the manufacturing process of the multilayer film. In some embodiments, the multilayer film may have a thickness of less than 500 micrometers (μm or micron). In other embodiments, the multilayer film may have a thickness of 15 μm to 500 μm, or 15 μm to 260 μm. In other embodiments, the multilayer film may have an overall thickness of 15μm~200μm, 15μm~150μm, 15μm~100μm, 15μm~50μm, 50μm~500μm, 50μm~260μm, 50μm~200μm, 50μm~150μm, 50μm~100μm, 100μm~500μm, 100μm~260μm, 100μm~200μm, 100μm~150μm, 150μm~500μm, 150μm~260μm, 150μm~200μm, 200μm~500μm, 200μm~260μm, or 260μm~500μm.
[0033] The multilayer films of this disclosure may have an overall density that depends on a number of factors, including, for example, the number of layers in the multilayer film, the composition of the layers in the multilayer film, the desired properties of the multilayer film, the desired end use of the film, and the manufacturing process of the multilayer film. In embodiments, the multilayer film has a density of at least 0.925 grams (g / cm³) per cubic centimeter. 3 ) may have an overall density of . In other embodiments, the overall density of the multilayer film is 0.925 g / cm³. 3 ~0.960g / cm 3 , 0.925 g / cm³ 3 ~0.940g / cm 3 , 0.925 g / cm³ 3 ~0.935g / cm 3 , 0.925 g / cm³ 3 ~0.930g / cm 3 , 0.930 g / cm³ 3 ~0.940g / cm 3 , 0.930 g / cm³ 3 ~0.935g / cm 3 , or 0.935 g / cm³3 ~0.940g / cm 3 It is possible.
[0034] The multilayer films of this disclosure may have relatively good dirt strength when measured according to ASTM D1709 Method A. In one embodiment, the multilayer film may have a dirt drop impact of at least 300 grams when measured according to ASTM D1709 Method A. In another embodiment, the multilayer film may have dirt drop impacts of 600 to 2000 grams, 600 to 1500 grams, 600 to 1000 grams, 700 to 2000 grams, 700 to 1500 grams, 700 to 1000 grams, 1000 to 2000 grams, 1000 to 1500 grams, or 1500 to 2000 grams when measured according to ASTM D1709 Method A. In a further embodiment, the multilayer films of this disclosure may have relatively good dirt strength when measured according to ASTM D1709 Method B. In one embodiment, the multilayer film may have a dirt drop impact of at least 300 grams when measured according to ASTM D1709 Method B. In another embodiment, the multilayer film may have a dirt drop impact of 400 to 2000 grams, 400 to 1500 grams, 400 to 1000 grams, 700 to 2000 grams, 700 to 1500 grams, 700 to 1000 grams, 1000 to 2000 grams, 1000 to 1500 grams, or 1500 to 2000 grams when measured according to ASTM D1709 Method A.
[0035] The multilayer films of this disclosure may have a cross-directional tensile creep of less than 50% when measured according to ASTM 2990. In other embodiments, the multilayer films may have a tensile creep of less than 40% or less than 30% when measured according to ASTM 2990.
[0036] The multilayer film of this disclosure, when measured according to the test method described later in this disclosure, has a density of 40 ft*lbf / in 3It may have a puncture energy at break exceeding 50 ft*lbf / in when measured according to the test method described later in this disclosure. 3 Or 60 ft * lbf / in 3 It may have a puncture energy exceeding that at the time of fracture.
[0037] The multilayer film of this disclosure may have a mechanical mean secant coefficient of at least 50,000 psi when measured according to ASTM D882. In other embodiments, the multilayer film may have a mechanical mean secant coefficient of at least 55,000 psi or 60,000 psi when measured according to ASTM D882. The multilayer film of this disclosure may have a cross mean secant coefficient of at least 55,000 psi when measured according to ASTM D882. In other embodiments, the multilayer film may have a cross mean secant coefficient of at least 60,000 psi or 70,000 psi when measured according to ASTM D882.
[0038] core layer As described above, the multilayer films of this disclosure may include a core layer. In a multilayer film designated as a three-layer structure, A / B / C, the core layer may be designated as B. In some embodiments, the core layer may be referred to as the “first layer”. In further embodiments, the core layer may be in direct contact with one or both of the second and third layers.
[0039] The core layer of the multilayer film of this disclosure can have a variety of thicknesses. The thickness of the core layer may depend on a number of factors, including, for example, the composition of the core layer, the desired overall properties of the multilayer film, the desired end use of the multilayer film, and the manufacturing process of the multilayer film. In embodiments, the core layer may have a thickness of 0.5 micrometers (μm or micron) to 60 μm. In other embodiments, the second layer may have a thickness of 0.5 μm to 50 μm, 0.5 μm to 25 μm, 0.5 μm to 10 μm, 0.5 μm to 5 μm, 0.5 μm to 1.0 μm, 1.0 μm to 50 μm, 1.0 μm to 25 μm, 1.0 μm to 10 μm, 1.0 μm to 5 μm, 5 μm to 50 μm, 5 μm to 25 μm, 5 μm to 10 μm, 10 μm to 50 μm, 10 μm to 25 μm, or 25 μm to 50 μm.
[0040] The core layer of the multilayer film disclosed herein may constitute 5% to 90% by weight of the total weight of the multilayer film. In some embodiments, the core layer may constitute 5% to 70% by weight, 5% to 60% by weight, 5% to 50% by weight, 5% to 40% by weight, 5% to 30% by weight, 5% to 20% by weight, 5% to 10% by weight, 10% to 40% by weight, 10% to 30% by weight, 10% to 20% by weight, 20% to 40% by weight, 20% to 30% by weight, or 30% to 40% by weight of the total weight of the multilayer film.
[0041] The core layer may include a polyethylene composition, which will be described in more detail later in this disclosure. The polyethylene composition may exhibit a balance between toughness and tear strength, thereby enabling multilayer films with improved abuse properties (i.e., dig, puncture energy, tear). For example, the polyethylene composition of this disclosure may have high dig strength at relatively high densities. As will be described in more detail later in this disclosure, such improved properties may include improved creep, elongation, and toughness. These improved properties may further enable multilayer films that can be produced using less material ("down gauge," i.e., using thinner film thickness) or using a simpler process compared to conventional multilayer films.
[0042] In one or more embodiments, the core layer may contain at least 50% by weight of polyethylene composition, based on the total weight of the core layer. In some embodiments, the core layer may contain polyethylene composition in amounts of about 10% to about 100% by weight, about 10% to about 80% by weight, about 10% to about 60% by weight, about 10% to about 40% by weight, about 10% to about 20% by weight, about 20% to about 100% by weight, about 20% to about 80% by weight, about 20% to about 60% by weight, about 20% to about 40% by weight, about 40% to about 100% by weight, about 40% to about 80% by weight, about 40% to about 60% by weight, about 60% to about 100% by weight, or about 80% to about 100% by weight, based on the total weight of the core layer.
[0043] In some embodiments, the core layer may include a blend of one or more additional materials with the polyethylene composition. In embodiments, the blend may include high-density polyethylene (HDPE), low-density polyethylene (LDPE), or a combination thereof.
[0044] Optionally, in some embodiments, the core layer may include high-density polyethylene (HDPE). Incorporating high-density polyethylene into the core layer can increase its rigidity. In some applications, it may be important that the multilayer film has sufficient rigidity, for example, as indicated by its tensile modulus, to prevent deformation and breakage.
[0045] In this embodiment, the high-density polyethylene measured according to ASTM D792 was 0.935 g / cm³. 3 ~Maximum approx. 0.980g / cm 3 It has a density of 0.935 g / cm³. In another embodiment, the density of high-density polyethylene is 0.935 g / cm³. 3 ~0.970g / cm 3 , 0.935 g / cm³ 3 ~0.960g / cm 3 , 0.935 g / cm³ 3 ~0.950g / cm 3 , 0.935 g / cm³ 3~0.940g / cm 3 , 0.940 g / cm³ 3 ~0.980g / cm 3 , 0.940 g / cm³ 3 ~0.970g / cm 3 , 0.940 g / cm³ 3 ~0.960g / cm 3 , 0.940 g / cm³ 3 ~0.950g / cm 3 , 0.950 g / cm³ 3 ~0.980g / cm 3 , 0.950 g / cm³ 3 ~0.970g / cm 3 , 0.950 g / cm³ 3 ~0.960g / cm 3 , 0.960 g / cm³ 3 ~0.980g / cm 3 , 0.960 g / cm³ 3 ~0.970g / cm 3 , 0.970 g / cm³ 3 ~0.980g / cm 3 It is possible.
[0046] In one or more embodiments, the core layer may contain high-density polyethylene having a melt index (I2) of 0.1 grams per 10 minutes (g / 10 min) to 10.0 g / 10 min when measured according to ASTM D1238 at a load of 2.16 kg and a temperature of 190 °C. It is also intended that the melt index (I2) of the high-density polyethylene may be 0.1 g / 10 min to 5.0 g / 10 min, 0.1 g / 10 min to 1.0 g / 10 min, 1.0 g / 10 min to 10.0 g / 10 min, 1.0 g / 10 min to 5.0 g / 10 min, or 5.0 g / 10 min to 10.0 g / 10 min.
[0047] Various methodologies are being considered for the production of high-density polyethylene. For example, high-density polyethylene resin can be produced using single-site catalysts, including but not limited to Ziegler-Natta catalyst systems, chromium catalysts, or bismetallocene catalysts and bound geometric catalysts.
[0048] In one or more embodiments, the core layer may contain up to 50% by weight of high-density polyethylene based on the total weight of the core layer. In some embodiments, the core layer may contain from about 0% to about 50%, from about 0% to about 40%, from about 0% to about 20%, from about 20% to about 50%, from about 20% to about 40%, or from about 40% to about 50% by weight of high-density polyethylene based on the total weight of the core layer.
[0049] Optionally, in some embodiments, the core layer may contain low-density polyethylene (LDPE). In one or more embodiments, the low-density polyethylene may have a melt index of from 0.1 g / 10 min to 10.0 g / 10 min when measured according to ASTM D1238 at a load of 2.16 kg and a temperature of 190 °C. In other embodiments, the low-density polyethylene may have a melt index of from 0.1 g / 10 min to 5.0 g / 10 min, or from 0.5 g / 10 min to 5.0 g / 10 min, or from 0.5 g / 10 min to 2.0 g / 10 min. In an embodiment, the low-density polyethylene may have a density of from 0.916 g / cm 3 ~ 0.935 g / cm 3 when measured according to ASTM D792. In another embodiment, the low-density polyethylene may have a density of from 0.916 g / cm 3 ~ 0.925 g / cm 3 when measured according to ASTM D792.
[0050] In one or more embodiments, the core layer may contain less than 50% by weight of low-density polyethylene based on the total weight of the core layer. In some embodiments, the core layer may contain from about 0% to about 50%, from about 0% to about 40%, from about 0% to about 20%, from about 20% to about 50%, from about 20% to about 40%, or from about 40% to about 50% by weight of low-density polyethylene based on the total weight of the core layer.
[0051] Outer layer As described above, the multilayer films of this disclosure may include an outer layer, which may also be referred to as a “skin layer.” The outer layer may include a second layer and a third layer. In a multilayer film designated as a three-layer structure, A / B / C, the outer layers may be designated as A and C. The second layer may be designated as A. The third layer may be designated as C. In further embodiments, the second layer, the third layer, or both may be the outermost layer of the multilayer film. In further embodiments, the second layer, the third layer, or both may be in direct contact with the first layer.
[0052] The second layer, third layer, or both of the multilayer film may each have a thickness of 0.5 micrometers (μm or micron) to 60 μm. In other embodiments, the second layer, third layer, or both of the multilayer film may have a thickness of 0.5 μm to 50 μm, 0.5 μm to 25 μm, 0.5 μm to 10 μm, 0.5 μm to 5 μm, 0.5 μm to 1.0 μm, 1.0 μm to 50 μm, 1.0 μm to 25 μm, 1.0 μm to 10 μm, 1.0 μm to 5 μm, 5 μm to 50 μm, 5 μm to 25 μm, 5 μm to 10 μm, 10 μm to 50 μm, 10 μm to 25 μm, or 25 μm to 50 μm.
[0053] The second layer, the third layer, or both of the multilayer film may constitute 5% to 90% by weight of the total weight of the multilayer film. In some embodiments, the second layer, the third layer, or both of the multilayer film of exemplary embodiment 1 may constitute 10% to 90% by weight, 20% to 80% by weight, 30% to 60% by weight, or 30% to 40% by weight of the total weight of the multilayer film.
[0054] In various embodiments, the second layer, the third layer, or both may include one or more materials that impart properties to the multilayer film that assist in stretching, processability, and the like. In some embodiments, the second layer and the third layer may include the same material. In other embodiments, the second layer and the third layer may include different materials. In an embodiment, the second layer may include a first polyolefin. In an embodiment, the third layer may include a second polyolefin. The first polyolefin and the second polyolefin may be the same or different in composition. In some embodiments, the first polyolefin, the second polyolefin, or both may include polyethylene having a density of 0.900 g / cm 3 to 0.970 g / cm 3 . In some embodiments, the polyethylene of the second layer, the third layer, or both may include one or more of LLDPE, HDPE, MDPE, and LDPE.
[0055] In one or more embodiments, the second layer, the third layer, or both may include linear low density polyethylene (LLDPE) having a density of 0.905 g / cm 3 to 0.930 g / cm 3 when measured according to ASTM D792. In another embodiment, the density of the linear low density polyethylene is 0.905 g / cm 3 to 0.925 g / cm 3 , 0.905 g / cm 3 to 0.920 g / cm 3 , 0.905 g / cm 3 to 0.915 g / cm 3 , 0.905 g / cm 3 to 0.910 g / cm 3 , 0.910 g / cm 3 to 0.930 g / cm 3 , 0.910 g / cm 3 to 0.925 g / cm 3 , 0.910 g / cm 3 to 0.920 g / cm 3 , 0.910 g / cm 3 to 0.915 g / cm 3 , 0.915 g / cm 3~0.930g / cm 3 , 0.915 g / cm³ 3 ~0.925g / cm 3 , 0.915 g / cm³ 3 ~0.920g / cm 3 , 0.920 g / cm³ 3 ~0.930g / cm 3 , 0.920 g / cm³ 3 ~0.925g / cm 3 , 0.925 g / cm³ 3 ~0.930g / cm 3 It is possible.
[0056] In one or more embodiments, the second layer, the third layer, or both may contain linear low-density polyethylene (LLDPE) having a melt index (I2) of 0.2 grams per 10 minutes (g / 10 min) to 2.0 g / 10 min, as measured according to ASTM D1238. It is also intended that the melt index (I2) of linear low-density polyethylene may be 0.2g / 10 min to 1.5g / 10 min, 0.2g / 10 min to 1.0g / 10 min, 0.2g / 10 min to 0.5g / 10 min, 0.5g / 10 min to 2.0g / 10 min, 0.5g / 10 min to 1.5g / 10 min, 0.5g / 10 min to 1.0g / 10 min, 1.0g / 10 min to 2.0g / 10 min, 1.0g / 10 min to 1.5g / 10 min, or 1.5g / 10 min to 2.0g / 10 min.
[0057] According to one embodiment, the linear low-density polyethylene may have a molecular weight distribution in the range of 3.5 to 5.5, expressed as the ratio of weight-average molecular weight to log-average molecular weight (Mw / Mn). In an additional embodiment, the linear low-density polyethylene may have a molecular weight distribution in the range of 3.5 to 4.5 or 4.5 to 5.5.
[0058] According to one or more additional embodiments, linear low-density polyethylene may have a zero shear viscosity ratio of 1.2 to 3.0 when measured according to the test methods described herein. In other embodiments, linear low-density polyethylene may have a zero shear viscosity ratio of 1.2 to 2.5, 1.2 to 2.0, 2.0 to 3.0, 2.0 to 2.5, or 2.5 to 3.0.
[0059] Various methodologies are being considered for the production of linear low-density polyethylene. For example, linear low-density polyethylene resins may be produced using resins made with single-site catalysts, including but not limited to Ziegler-Natta catalyst systems, bismetallocene catalysts, and bound geometric catalysts, or resins made with post-metallocene molecular catalysts. Linear low-density polyethylene resins may include linear, substantially linear, or heterogeneous polyethylene copolymers or homopolymers. Linear low-density polyethylene resins include substantially linear polyethylene, which contains fewer long-chain branches than LDPE and is further defined in U.S. Patents 5,272,236, 5,278,272, 5,582,923, and 5,733,155; homogeneous branched linear ethylene polymer compositions, such as those in U.S. Patent 3,645,992; heterogeneous branched ethylene polymers, such as those prepared according to the process disclosed in U.S. Patent 4,076,698; and blends thereof (such as those disclosed in U.S. Patents 3,914,342 or 5,854,045). Linear low-density polyethylene resins can be produced by gas-phase, solution-phase, or slurry polymerization, or any combination thereof, using any type of reactor or reactor configuration known in the art.
[0060] In one or more embodiments, the second layer, the third layer, or both may contain 0% to 100% by weight of linear low-density polyethylene, based on the total weight of each layer. In some embodiments, the second layer, the third layer, or both may contain LLDPE in amounts of about 50% to 100% by weight, about 50% to 80% by weight, about 50% to 60% by weight, about 60% to 100% by weight, about 60% to 80% by weight, or about 80% to 100% by weight, based on the total weight of each layer.
[0061] Optionally, in some embodiments, the second layer, the third layer, or both may have a viscosity of 0.935 g / cm³ when measured according to ASTM D792. 3~Maximum approx. 0.980g / cm 3 It may include high-density polyethylene (HDPE) having a density of 0.935 g / cm³. In another embodiment, the density of the high-density polyethylene is 0.935 g / cm³. 3 ~0.970g / cm 3 , 0.935 g / cm³ 3 ~0.960g / cm 3 , 0.935 g / cm³ 3 ~0.950g / cm 3 , 0.935 g / cm³ 3 ~0.940g / cm 3 , 0.940 g / cm³ 3 ~0.980g / cm 3 , 0.940 g / cm³ 3 ~0.970g / cm 3 , 0.940 g / cm³ 3 ~0.960g / cm 3 , 0.940 g / cm³ 3 ~0.950g / cm 3 , 0.950 g / cm³ 3 ~0.980g / cm 3 , 0.950 g / cm³ 3 ~0.970g / cm 3 , 0.950 g / cm³ 3 ~0.960g / cm 3 , 0.960 g / cm³ 3 ~0.980g / cm 3 , 0.960 g / cm³ 3 ~0.970g / cm 3 , or 0.970 g / cm³ 3 ~0.980g / cm 3 It is possible.
[0062] In one or more embodiments, the second layer, the third layer, or both may contain high-density polyethylene having a melt index (I2) of 0.1 grams per 10 minutes (g / 10 min) to 10.0 g / 10 min when measured according to ASTM D1238 at a load of 2.16 kg and a temperature of 190 °C. It is also intended that the melt index (I2) of the high-density polyethylene may be 0.1 g / 10 min to 5.0 g / 10 min, 0.1 g / 10 min to 1.0 g / 10 min, 1.0 g / 10 min to 10.0 g / 10 min, 1.0 g / 10 min to 5.0 g / 10 min, or 5.0 g / 10 min to 10.0 g / 10 min.
[0063] Various methodologies are being considered for the production of high-density polyethylene. For example, high-density polyethylene resin can be produced using single-site catalysts, including but not limited to Ziegler-Natta catalyst systems, chromium catalysts, or bismetallocene catalysts and bound geometric catalysts.
[0064] In one or more embodiments, the second layer, the third layer, or both may contain up to 50% by weight of high-density polyethylene, based on the total weight of each layer. In some embodiments, the second layer, the third layer, or both may contain high-density polyethylene in amounts of about 0% to about 50% by weight, about 0% to about 40% by weight, about 0% to about 20% by weight, about 20% to about 50% by weight, about 20% to about 40% by weight, or about 40% to about 50% by weight, based on the total weight of each layer.
[0065] Optionally, in some embodiments, the second layer, the third layer, or both may include medium-density polyethylene (MDPE). In one or more embodiments, the MDPE may have a melt index of 0.1 g / 10 min to 10.0 g / 10 min when measured according to ASTM D1238 at a load of 2.16 kg and a temperature of 190 °C. In other embodiments, the MDPE may have a melt index of 0.1 g / 10 min to 5.0 g / 10 min, or 0.5 g / 10 min to 5.0 g / 10 min, or 0.5 g / 10 min to 2.0 g / 10 min. In embodiments, the MDPE may have a melt index of 0.924 g / cm³ when measured according to ASTM D792. 3 ~0.942 g / cm³ 3 It may have a density of 0.924 g / cm³. In another embodiment, low-density polyethylene may have a density of 0.924 g / cm³. 3 ~0.936 g / cm³ 3 It may have a density of .
[0066] In one or more embodiments, the second layer, the third layer, or both may contain less than 50% by weight of medium-density polyethylene, based on the total weight of each layer. In some embodiments, the second layer, the third layer, or both may contain about 0% to about 100% by weight, about 0% to about 80% by weight, about 0% to about 60% by weight, about 0% to about 0% by weight, about 0% to about 20% by weight, about 10% to about 100% by weight, about 10% to about 80% by weight, about 10% to about 60% by weight, about 10% to about 40% by weight, and about 1 It may contain MDPE in amounts of 0% to approximately 20% by weight, approximately 20% to approximately 100% by weight, approximately 20% to approximately 80% by weight, approximately 20% to approximately 60% by weight, approximately 20% to approximately 40% by weight, approximately 40% to approximately 100% by weight, approximately 40% to approximately 80% by weight, approximately 40% to approximately 60% by weight, approximately 60% to approximately 100% by weight, approximately 60% to approximately 80% by weight, or approximately 80% to approximately 100% by weight.
[0067] The second layer, the third layer, or both may include a polyethylene composition, which will be described in more detail later in this disclosure. The polyethylene composition may exhibit a balance between toughness and tear strength, thereby enabling multilayer films with improved abuse properties (i.e., dig, puncture energy, tear). For example, the polyethylene composition of this disclosure may have high dig strength at relatively high densities. As will be described in more detail later, such improved properties may include improved creep, stretch, and toughness. These improved properties may further enable multilayer films that can be produced using less material ("down gauge," i.e., using thinner film thickness) or using a simpler process compared to conventional multilayer films.
[0068] In one or more embodiments, the second layer, the third layer, or both are based on the total weight of each layer, with weights of approximately 0% to approximately 100%, approximately 0% to approximately 80%, approximately 0% to approximately 60%, approximately 0% to approximately 0%, approximately 0% to approximately 20%, approximately 10% to approximately 100%, approximately 10% to approximately 80%, approximately 10% to approximately 60%, approximately 10% to approximately 40%, and approximately 10% It may contain polyethylene compositions in amounts of % to approximately 20% by weight, approximately 20% to approximately 100% by weight, approximately 20% to approximately 80% by weight, approximately 20% to approximately 60% by weight, approximately 20% to approximately 40% by weight, approximately 40% to approximately 100% by weight, approximately 40% to approximately 80% by weight, approximately 40% to approximately 60% by weight, approximately 60% to approximately 100% by weight, approximately 60% to approximately 80% by weight, or approximately 80% to approximately 100% by weight.
[0069] Optionally, in some embodiments, the second layer, the third layer, or both may include low-density polyethylene (LDPE). In one or more embodiments, the LDPE may have a melt index of 0.1 g / 10 min to 10.0 g / 10 min when measured according to ASTM D1238 at a load of 2.16 kg and a temperature of 190 °C. In other embodiments, the LDPE may have a melt index of 0.1 g / 10 min to 5.0 g / 10 min, or 0.5 g / 10 min to 5.0 g / 10 min, or 0.5 g / 10 min to 2.0 g / 10 min. In embodiments, the LDPE may have a melt index of 0.916 g / cm³ when measured according to ASTM D792. 3 ~0.935g / cm 3 It may have a density of 0.916 g / cm³. In another embodiment, low-density polyethylene may have a density of 0.916 g / cm³. 3 ~0.925g / cm 3 It may have a density of .
[0070] In one or more embodiments, the second layer, the third layer, or both may contain less than 50% by weight of low-density polyethylene, based on the total weight of each layer. In some embodiments, the second layer, the third layer, or both may contain low-density polyethylene in amounts of about 0% to about 50% by weight, about 0% to about 40% by weight, about 0% to about 20% by weight, about 20% to about 50% by weight, about 20% to about 40% by weight, or about 40% to about 50% by weight, based on the total weight of each layer.
[0071] Additional layer As described above, in some embodiments, the multilayer film may include one or more additional layers. In some embodiments, the multilayer film of the present disclosure may include up to 11, 13, 15, or more layers.
[0072] One or more additional layers may comprise one or more materials that impart properties to the multilayer film that aid in stretchability, processability, rigidity, etc. In some embodiments, one or more additional layers may comprise one or more polyolefins. In some embodiments, the amount of polyolefins is 0.900 g / cm³. 3~0.970g / cm 3 It may contain one or more polyethylene having a density of . In some embodiments, one or more polyethylene in one or more additional layers may include LLDPE, HDPE, MDPE, LDPE, polyethylene compositions, and combinations thereof.
[0073] In some embodiments, the multilayer film may optionally include tie layers to facilitate adhesion between layers. In some embodiments, the tie layers may be positioned between the core layer and each outer layer. In a multilayer film designated as A / Tie1 / B / Tie2 / C, the core layer may be designated as B, the outer layers as A and C, and the tie layers as Tie1 and Tie2. The second layer may be designated as A. The third layer may be designated as C. In further embodiments, the second layer, the third layer, or both may be the outermost layers of the multilayer film. In further embodiments, the first tie layer (Tie1) may be in direct contact with one or both of the first and second layers. In further embodiments, the second tie layer (Tie2) may be in direct contact with one or both of the first and third layers. In some such embodiments, the tie layers may include maleic anhydride grafted polyethylene or other functionalized resins known to be useful as tie layers. A suitable example of a commercially available maleic anhydride grafted polyethylene is AMPLIFY® TY1057 from The Dow Chemical Company (Midland, MI), and others known to those skilled in the art may also be used.
[0074] In some embodiments, the multilayer film may optionally include a barrier. A preferred barrier layer may be selected from layers comprising an ethylene vinyl alcohol copolymer, a cyclic olefin copolymer, polyvinyl acetate, or a blend of one or more of these polymers with polyethylene, polyvinyl alcohol, or polyamide.
[0075] Exemplary Embodiment 1 As mentioned above, there is a need for multilayer films that exhibit physical properties such as dirt / bag drop resistance, puncture resistance, tear resistance, and creep resistance, meeting customer and industry requirements. In some embodiments, these multilayer films can still maintain the physical properties that meet customer and industry requirements even with reduced thickness.
[0076] Hereinafter, an embodiment of the multilayer film described herein, referred to herein as “Exemplary Embodiment 1,” is used. Exemplary Embodiment 1 may comprise a first layer comprising a polyethylene composition, a second layer comprising a first linear low-density polyethylene, and a third layer comprising a second linear low-density polyethylene. The core layer of Exemplary Embodiment 1 may comprise a polyethylene composition, which is described in more detail herein. While used in the film, the polyethylene composition may exhibit a balance of toughness and stiffness, thereby enabling the Exemplary Embodiment 1 multilayer film to have improved abuse properties (i.e., dig, puncture energy, tear). For example, the use of the polyethylene composition of this disclosure provides a core layer exhibiting relatively high dig strength at relatively high density. These improved properties may further enable embodiments of the Exemplary Embodiment 1 multilayer film that can be produced using less material (i.e., “down gauge,” i.e., using a thinner film thickness) or using a simpler process compared to conventional multilayer films.
[0077] The multilayer film of exemplary embodiment 1 can have a variety of thicknesses. In further embodiments, the multilayer film of exemplary embodiment 1 may have a thickness of less than 150 micrometers (μm or micron). In other embodiments, the multilayer film may have a thickness of 15 μm to 120 μm. In other embodiments, the multilayer film may have an overall thickness of 25 μm to 100 μm, 25 μm to 75 μm, 25 μm to 50 μm, 50 μm to 150 μm, 50 μm to 100 μm, 50 μm to 75 μm, 75 μm to 150 μm, 75 μm to 100 μm, or 100 μm to 150 μm.
[0078] In the embodiment, the multilayer film of exemplary embodiment 1 has a density of at least 0.925 grams (g / cm³) per cubic centimeter. 3 ) may have an overall density of . In other embodiments, the overall density of the multilayer film of exemplary embodiment 1 is 0.925 g / cm³. 3 ~0.940g / cm 3 , 0.925 g / cm³ 3 ~0.935g / cm 3 , 0.925 g / cm³ 3 ~0.930g / cm 3 , 0.930 g / cm³ 3 ~0.940g / cm 3 , 0.930 g / cm³ 3 ~0.935g / cm 3 , or 0.935 g / cm³ 3 ~0.940g / cm 3 It is possible.
[0079] In one embodiment, the multilayer film of exemplary embodiment 1 may have a relatively good dirt strength when measured according to ASTM D1709 Method B. In another embodiment, the multilayer film of exemplary embodiment 1 may have a dirt drop impact of at least 400 grams when measured according to ASTM D1709 Method B. In yet another embodiment, the multilayer film of exemplary embodiment 1 may have dirt drop impacts of 400 to 2000 grams, 400 to 1500 grams, 400 to 1000 grams, 700 to 2000 grams, 700 to 1500 grams, 700 to 1000 grams, 1000 to 2000 grams, 1000 to 1500 grams, or 1500 to 2000 grams when measured according to ASTM D1709 Method A.
[0080] The multilayer film of Exemplary Embodiment 1 may have a mechanical mean secant coefficient of at least 50,000 psi when measured according to ASTM D882. In other embodiments, the multilayer film may have a mechanical mean secant coefficient of at least 55,000 psi or 60,000 psi when measured according to ASTM D882. The multilayer film of the present disclosure may have a cross mean secant coefficient of at least 55,000 psi when measured according to ASTM D882. In other embodiments, the multilayer film may have a cross mean secant coefficient of at least 60,000 psi or 70,000 psi when measured according to ASTM D882.
[0081] In the exemplary embodiment 1, the core layer of the multilayer film may have a thickness of 0.5 micrometers (μm or micron) to 60 μm. In other embodiments, the core layer may have a thickness of 0.5 μm to 50 μm, 0.5 μm to 25 μm, 0.5 μm to 10 μm, 0.5 μm to 5 μm, 0.5 μm to 1.0 μm, 1.0 μm to 50 μm, 1.0 μm to 25 μm, 1.0 μm to 10 μm, 1.0 μm to 5 μm, 5 μm to 50 μm, 5 μm to 25 μm, 5 μm to 10 μm, 10 μm to 50 μm, 10 μm to 25 μm, or 25 μm to 50 μm.
[0082] The core layer of the multilayer film of Exemplary Embodiment 1 may constitute 10% to 80% by weight of the total weight of the multilayer film of Exemplary Embodiment 1. In some embodiments, the core layer may constitute 10% to 60% by weight, 10% to 40% by weight, 10% to 30% by weight, 10% to 20% by weight, 20% to 80% by weight, 20% to 40% by weight, 20% to 30% by weight, 30% to 80% by weight, 30% to 60% by weight, or 30% to 40% by weight of the total weight of the multilayer film of Exemplary Embodiment 1.
[0083] In one or more embodiments, the core layer of Exemplary Embodiment 1 may contain at least 10% by weight of polyethylene composition, based on the total weight of the core layer. In some embodiments, the core layer may contain polyethylene composition in amounts of about 10% to about 100% by weight, about 10% to about 80% by weight, about 10% to about 60% by weight, about 10% to about 40% by weight, about 10% to about 20% by weight, about 20% to about 100% by weight, about 20% to about 80% by weight, about 20% to about 60% by weight, about 20% to about 40% by weight, about 40% to about 100% by weight, about 40% to about 80% by weight, about 40% to about 60% by weight, about 60% to about 100% by weight, or about 80% to about 100% by weight, based on the total weight of the core layer.
[0084] Optionally, in some embodiments, the core layer of exemplary Embodiment 1 may include low-density polyethylene (LDPE). In one or more embodiments, the core layer may contain less than 50% by weight of LDPE based on the total weight of the core layer. In some embodiments, the core layer of exemplary Embodiment 1 may contain LDPE in amounts of about 0% to about 50% by weight, about 0% to about 40% by weight, about 0% to about 20% by weight, about 20% to about 50% by weight, about 20% to about 40% by weight, or about 40% to about 50% by weight, based on the total weight of the core layer.
[0085] In the exemplary embodiment 1, the second layer, the third layer, or both of the multilayer film may each have a thickness of 0.5 micrometers (μm or micron) to 60 μm. In other embodiments, the second layer, the third layer, or both of the multilayer film in exemplary embodiment 1 may have a thickness of 0.5 μm to 50 μm, 0.5 μm to 25 μm, 0.5 μm to 10 μm, 0.5 μm to 5 μm, 0.5 μm to 1.0 μm, 1.0 μm to 50 μm, 1.0 μm to 25 μm, 1.0 μm to 10 μm, 1.0 μm to 5 μm, 5 μm to 50 μm, 5 μm to 25 μm, 5 μm to 10 μm, 10 μm to 50 μm, 10 μm to 25 μm, or 25 μm to 50 μm.
[0086] The second layer, third layer, or both of the multilayer film of Exemplary Embodiment 1 may constitute 10% to 90% by weight of the total weight of the multilayer film of Exemplary Embodiment 1. In some embodiments, the second layer, third layer, or both of the multilayer film of Exemplary Embodiment 1 may constitute 20% to 80% by weight, 30% to 60% by weight, or 30% to 40% by weight of the total weight of the multilayer film of Exemplary Embodiment 1.
[0087] In one or more embodiments, the second layer, the third layer, or both may contain more than 50% by weight of linear low-density polyethylene, based on the total weight of each layer. In some embodiments, the second layer, the third layer, or both may contain LLDPE in amounts of about 50% to about 100% by weight, about 50% to about 80% by weight, about 50% to about 60% by weight, about 60% to about 100% by weight, about 60% to about 80% by weight, or about 80% to about 100% by weight, based on the total weight of each layer.
[0088] Optionally, in some embodiments, the second layer, the third layer, or both of the exemplary embodiment 1 may contain low-density polyethylene (LDPE). In one or more embodiments, the second layer, the third layer, or both may contain less than 50% by weight of LDPE based on the total weight of each layer. In some embodiments, the second layer, the third layer, or both of the exemplary embodiment 1 may contain LDPE in amounts of about 0% to about 50% by weight, about 0% to about 40% by weight, about 0% to about 20% by weight, about 20% to about 50% by weight, about 20% to about 40% by weight, or about 40% to about 50% by weight, based on the total weight of each layer.
[0089] Exemplary Embodiment 2 As mentioned above, there is a need for multilayer films that exhibit physical properties such as dirt / bag drop resistance, puncture resistance, tear resistance, and creep resistance, meeting customer and industry requirements. In some embodiments, these multilayer films can still maintain the physical properties that meet customer and industry requirements even with reduced thickness.
[0090] Hereinafter, an embodiment of the multilayer film described herein, referred to herein as “Exemplary Embodiment 2,” is used. Exemplary Embodiment 2 may comprise a first layer comprising a polyethylene composition and high-density polyethylene, a second layer comprising a first linear low-density polyethylene, and a third layer comprising a second linear low-density polyethylene. The core layer of Exemplary Embodiment 2 may comprise a polyethylene composition, which is described in more detail herein. The polyethylene composition may exhibit a balance between toughness and tear strength, thereby enabling the multilayer film of Exemplary Embodiment 2 to exhibit improved abuse properties (i.e., dig, puncture energy, tear). For example, the use of the polyethylene composition of this disclosure provides a core layer exhibiting relatively high dig strength at relatively high density. These improved properties may further enable embodiments of the multilayer film of Exemplary Embodiment 2 that can be produced using less material (i.e., “down gauge,” i.e., using a thinner film thickness) or using a simpler process compared to conventional multilayer films.
[0091] The multilayer film of exemplary embodiment 2 can have a variety of thicknesses. In further embodiments, the multilayer film of exemplary embodiment 2 may have a thickness of less than 500 micrometers (μm or micron). In other embodiments, the multilayer film may have a thickness of 15 μm to 500 μm, or 15 μm to 260 μm. In other embodiments, the multilayer film may have an overall thickness of 15μm~200μm, 15μm~150μm, 15μm~100μm, 15μm~50μm, 50μm~500μm, 50μm~260μm, 50μm~200μm, 50μm~150μm, 50μm~100μm, 100μm~500μm, 100μm~260μm, 100μm~200μm, 100μm~150μm, 150μm~500μm, 150μm~260μm, 150μm~200μm, 200μm~500μm, 200μm~260μm, or 260μm~500μm.
[0092] In the embodiment, the multilayer film of exemplary embodiment 1 has a density of at least 0.925 grams (g / cm³) per cubic centimeter. 3 ) may have an overall density of . In other embodiments, the overall density of the multilayer film of exemplary embodiment 2 is 0.925 g / cm³. 3 ~0.940g / cm 3 , 0.925 g / cm³ 3 ~0.935g / cm 3 , 0.925 g / cm³ 3 ~0.930g / cm 3 , 0.930 g / cm³ 3 ~0.940g / cm 3 , 0.930 g / cm³ 3 ~0.935g / cm 3 , or 0.935 g / cm³ 3 ~0.940g / cm 3 It is possible.
[0093] In one embodiment, the multilayer film of exemplary embodiment 2 may have a dirt drop impact of at least 600 grams when measured according to ASTM D1709 Method A. In another embodiment, the multilayer film of exemplary embodiment 2 may have a dirt drop impact of 600 to 2000 grams, 600 to 1500 grams, 600 to 1000 grams, 700 to 2000 grams, 700 to 1500 grams, 700 to 1000 grams, 1000 to 2000 grams, 1000 to 1500 grams, or 1500 to 2000 grams when measured according to ASTM D1709 Method A. In a further embodiment, the multilayer film of exemplary embodiment 2 may have a relatively good dirt strength when measured according to ASTM D1709 Method B. In one embodiment, the multilayer film of exemplary embodiment 2 may have a dirt drop impact of at least 400 grams when measured according to ASTM D1709 Method B. In other embodiments, the multilayer film of exemplary Embodiment 2 may have dirt drop impacts of 400-2000 grams, 400-1500 grams, 400-1000 grams, 700-2000 grams, 700-1500 grams, 700-1000 grams, 1000-2000 grams, 1000-1500 grams, or 1500-2000 grams when measured according to ASTM D1709 Method A.
[0094] The multilayer film of exemplary embodiment 2 may have a cross-directional tensile creep of less than 50% when measured according to ASTM 2990. In other embodiments, the multilayer film of exemplary embodiment 2 may have a tensile creep of less than 40% or less than 30% when measured according to ASTM 2990.
[0095] The multilayer film of exemplary embodiment 2 measured 30 ft*lbf / in when measured according to the test method described later in this disclosure. 3 It may have a puncture energy at break exceeding 40 ft*lbf / in when measured according to the test method described later in this disclosure.3 Or 50 ft * lbf / in 3 It may have a puncture energy exceeding that at the time of fracture.
[0096] The multilayer film of exemplary embodiment 2 may have a mechanical mean secant coefficient of at least 50,000 psi when measured according to ASTM D882. In other embodiments, the multilayer film may have a mechanical mean secant coefficient of at least 55,000 psi or 60,000 psi when measured according to ASTM D882. The multilayer film of the present disclosure may have a cross mean secant coefficient of at least 55,000 psi when measured according to ASTM D882. In other embodiments, the multilayer film may have a cross mean secant coefficient of at least 60,000 psi or 70,000 psi when measured according to ASTM D882.
[0097] In the exemplary embodiment 2, the core layer of the multilayer film may have a thickness of 0.5 micrometers (μm or micron) to 60 μm. In other embodiments, the second layer may have a thickness of 0.5 μm to 50 μm, 0.5 μm to 25 μm, 0.5 μm to 10 μm, 0.5 μm to 5 μm, 0.5 μm to 1.0 μm, 1.0 μm to 50 μm, 1.0 μm to 25 μm, 1.0 μm to 10 μm, 1.0 μm to 5 μm, 5 μm to 50 μm, 5 μm to 25 μm, 5 μm to 10 μm, 10 μm to 50 μm, 10 μm to 25 μm, or 25 μm to 50 μm.
[0098] The core layer of the multilayer film of Exemplary Embodiment 2 may constitute 5% to 60% by weight of the total weight of the multilayer film of Exemplary Embodiment 2. In some embodiments, the core layer may constitute 5% to 30% by weight, 5% to 20% by weight, 5% to 10% by weight, 10% to 40% by weight, 10% to 30% by weight, 10% to 20% by weight, 20% to 40% by weight, 20% to 30% by weight, or 30% to 40% by weight of the multilayer film of Exemplary Embodiment 2.
[0099] In one or more embodiments, the core layer of exemplary embodiment 2 may contain at least 50% by weight of polyethylene composition, based on the total weight of the core layer. In some embodiments, the core layer may contain polyethylene composition in amounts of about 10% to about 100% by weight, about 10% to about 80% by weight, about 10% to about 60% by weight, about 10% to about 40% by weight, about 10% to about 20% by weight, about 20% to about 100% by weight, about 20% to about 80% by weight, about 20% to about 60% by weight, about 20% to about 40% by weight, about 40% to about 100% by weight, about 40% to about 80% by weight, about 40% to about 60% by weight, about 60% to about 100% by weight, or about 80% to about 100% by weight, based on the total weight of the core layer.
[0100] In some embodiments, the core layer of the exemplary Embodiment 2 may include high-density polyethylene (HDPE). In one or more embodiments, the core layer may contain up to 50% by weight of high-density polyethylene, based on the total weight of the core layer. In some embodiments, the core layer may contain high-density polyethylene in amounts of about 0% to about 50% by weight, about 0% to about 40% by weight, about 0% to about 20% by weight, about 20% to about 50% by weight, about 20% to about 40% by weight, or about 40% to about 50% by weight, based on the total weight of the core layer.
[0101] In exemplary embodiment 2, the second layer, third layer, or both of the multilayer film may each have a thickness of 0.5 micrometers (μm or micron) to 60 μm. In other embodiments, the second layer, third layer, or both of the multilayer film in exemplary embodiment 1 may have a thickness of 0.5 μm to 50 μm, 0.5 μm to 25 μm, 0.5 μm to 10 μm, 0.5 μm to 5 μm, 0.5 μm to 1.0 μm, 1.0 μm to 50 μm, 1.0 μm to 25 μm, 1.0 μm to 10 μm, 1.0 μm to 5 μm, 5 μm to 50 μm, 5 μm to 25 μm, 5 μm to 10 μm, 10 μm to 50 μm, 10 μm to 25 μm, or 25 μm to 50 μm.
[0102] The second layer, the third layer, or both of the multilayer film of Exemplary Embodiment 2 may constitute 5% to 40% by weight of the total weight of the multilayer film of Exemplary Embodiment 2. In some embodiments, the second layer, the third layer, or both of the multilayer film of Exemplary Embodiment 2 may constitute 5% to 30% by weight, 5% to 20% by weight, 5% to 10% by weight, 10% to 40% by weight, 10% to 30% by weight, 10% to 20% by weight, 20% to 40% by weight, 20% to 30% by weight, or 30% to 40% by weight of the total weight of the multilayer film of Exemplary Embodiment 2.
[0103] In one or more embodiments, the second layer, the third layer, or both of the exemplary embodiment 2 may contain about 0 to about 100% by weight of linear low-density polyethylene, based on the total weight of each layer. In some embodiments, the second layer, the third layer, or both of the exemplary embodiment 2 may contain about 5% to about 100% by weight, about 10% to about 90% by weight, about 20% to about 80% by weight, about 30% to about 70% by weight, or about 40% to about 50% by weight of LLDPE, based on the total weight of each layer.
[0104] In one or more embodiments, the second layer, third layer, or both of the exemplary embodiment 2 are based on the total weight of each layer, with weights of approximately 0% to approximately 100%, approximately 0% to approximately 80%, approximately 0% to approximately 60%, approximately 0% to approximately 0%, approximately 0% to approximately 20%, approximately 10% to approximately 100%, approximately 10% to approximately 80%, approximately 10% to approximately 60%, and approximately 10% to approximately 40%. It may contain MDPE in amounts of %, approximately 10% to 20% by weight, approximately 20% to 100% by weight, approximately 20% to 80% by weight, approximately 20% to 60% by weight, approximately 20% to 40% by weight, approximately 40% to 100% by weight, approximately 40% to 80% by weight, approximately 40% to 60% by weight, approximately 60% to 100% by weight, approximately 60% to 80% by weight, or approximately 80% to 100% by weight.
[0105] In one or more embodiments, the second layer, third layer, or both of the exemplary embodiment 2 are based on the total weight of each layer, with a weight of approximately 0% to approximately 100%, approximately 0% to approximately 80%, approximately 0% to approximately 60%, approximately 0% to approximately 0%, approximately 0% to approximately 20%, approximately 10% to approximately 100%, approximately 10% to approximately 80%, approximately 10% to approximately 60%, and approximately 10% to approximately 40%. It may contain polyethylene compositions in amounts of approximately 10% to 20% by weight, approximately 20% to 100% by weight, approximately 20% to 80% by weight, approximately 20% to 60% by weight, approximately 20% to 40% by weight, approximately 40% to 100% by weight, approximately 40% to 80% by weight, approximately 40% to 60% by weight, approximately 60% to 100% by weight, approximately 60% to 80% by weight, or approximately 80% to 100% by weight.
[0106] In one or more embodiments, the second layer, the third layer, or both of the exemplary embodiment 2 may contain less than 50% by weight of low-density polyethylene, based on the total weight of each layer. In some embodiments, the second layer, the third layer, or both of the exemplary embodiment 2 may contain high-density polyethylene in amounts of about 0% to about 50% by weight, about 0% to about 40% by weight, about 0% to about 20% by weight, about 20% to about 50% by weight, about 20% to about 40% by weight, or about 40% to about 50% by weight, based on the total weight of each layer.
[0107] Exemplary Embodiment 3 As mentioned above, there is a need for multilayer films that exhibit physical properties such as heat resistance, good gas barrier properties, high rigidity, and excellent toughness without using polyamides. Conventional multilayer films, when nylon is included in the film structure, exhibit film properties that strike a desirable balance between the dirt coefficient and the film coefficient, but they may also exhibit process complexity, complexity of the multilayer film structure, non-recyclable multilayer films, and higher material costs compared to other polyolefins.
[0108] Hereinafter, we refer to an embodiment of the multilayer film described herein, referred to herein as “Exemplary Embodiment 3.” Exemplary Embodiment 3 may comprise a first layer comprising a first polyethylene composition and a first high-density polyethylene, a second layer comprising a second polyethylene composition, a second high-density polyethylene, and a first low-density polyethylene, and a third layer comprising a third polyethylene composition and a second low-density polyethylene. Embodiments of the multilayer film of Exemplary Embodiment 3 comprising the polyethylene compositions disclosed herein may exhibit an excellent balance of film properties (dirt and coefficient) by exhibiting dirt equivalent to or better than that of multilayer films containing polyamide, while exhibiting improved coefficients.
[0109] The multilayer film of exemplary embodiment 3 can have various thicknesses. In a further embodiment, the multilayer film of exemplary embodiment 3 may have a thickness of 25 to 260 μm. In other embodiments, the multilayer film may have an overall thickness of 25 μm to 200 μm, 25 μm to 150 μm, 25 μm to 100 μm, 25 μm to 50 μm, 50 μm to 260 μm, 50 μm to 200 μm, 50 μm to 150 μm, 50 μm to 100 μm, 100 μm to 260 μm, 100 μm to 200 μm, 100 μm to 150 μm, 150 μm to 260 μm, 150 μm to 200 μm, or 200 μm to 260 μm.
[0110] In the embodiment, the multilayer film of exemplary embodiment 3 has a density of at least 0.925 grams (g / cm³) per cubic centimeter. 3 ) may have an overall density of . In other embodiments, the overall density of the multilayer film of exemplary embodiment 3 is 0.925 g / cm³. 3 ~0.940g / cm 3 , 0.925 g / cm³ 3 ~0.935g / cm 3 , 0.925 g / cm³ 3 ~0.930g / cm 3 , 0.930 g / cm³ 3 ~0.940g / cm 3 , 0.930 g / cm³ 3 ~0.935g / cm3 , or 0.935 g / cm³ 3 ~0.940g / cm 3 It is possible.
[0111] In one embodiment, the multilayer film of exemplary embodiment 3 may have a dirt drop impact of at least 300 grams when measured according to ASTM D1709 Method A. In another embodiment, the multilayer film of exemplary embodiment 3 may have a dirt drop impact of 300 to 1000 grams, 300 to 500 grams, 300 to 400 grams, 400 to 1000 grams, 400 to 1000 grams, or 400 to 500 grams when measured according to ASTM D1709 Method A. In yet another embodiment, the multilayer film of exemplary embodiment 3 may have a relatively good dirt strength when measured according to ASTM D1709 Method B. In one embodiment, the multilayer film of exemplary embodiment 3 may have a dirt drop impact of at least 300 grams when measured according to ASTM D1709 Method B. In other embodiments, the multilayer film of exemplary embodiment 3 may have a dirt drop impact of 300 to 1000 grams, 300 to 500 grams, 300 to 400 grams, 400 to 1000 grams, 400 to 1000 grams, or 400 to 500 grams when measured according to ASTM D1709 Method B.
[0112] The multilayer film of exemplary embodiment 3 may have a mechanical mean secant coefficient of at least 50,000 psi when measured according to ASTM D882. In other embodiments, the multilayer film may have a mechanical mean secant coefficient of at least 55,000 psi or 60,000 psi when measured according to ASTM D882. The multilayer film of the present disclosure may have a cross mean secant coefficient of at least 55,000 psi when measured according to ASTM D882. In other embodiments, the multilayer film may have a cross mean secant coefficient of at least 60,000 psi or 70,000 psi when measured according to ASTM D882.
[0113] In the exemplary embodiment 3, the core layer of the multilayer film may have a thickness of 0.5 micrometers (μm or micron) to 60 μm. In other embodiments, the second layer may have a thickness of 0.5 μm to 50 μm, 0.5 μm to 25 μm, 0.5 μm to 10 μm, 0.5 μm to 5 μm, 0.5 μm to 1.0 μm, 1.0 μm to 50 μm, 1.0 μm to 25 μm, 1.0 μm to 10 μm, 1.0 μm to 5 μm, 5 μm to 50 μm, 5 μm to 25 μm, 5 μm to 10 μm, 10 μm to 50 μm, 10 μm to 25 μm, or 25 μm to 50 μm.
[0114] The core layer of the multilayer film of Exemplary Embodiment 3 may constitute 30% to 80% by weight of the total weight of the multilayer film of Exemplary Embodiment 3. In some embodiments, the core layer may constitute 30% to 60% by weight, 30% to 40% by weight, 40% to 80% by weight, 40% to 60% by weight, or 60% to 80% by weight of the multilayer film of Exemplary Embodiment 3.
[0115] In one or more embodiments, the core layer of exemplary embodiment 3 may contain 40% to 100% by weight of polyethylene composition, based on the total weight of the core layer. In some embodiments, the core layer may contain polyethylene composition in amounts of about 10% to about 100% by weight, about 10% to about 80% by weight, about 10% to about 60% by weight, about 10% to about 40% by weight, about 10% to about 20% by weight, about 20% to about 100% by weight, about 20% to about 80% by weight, about 20% to about 60% by weight, about 20% to about 40% by weight, about 40% to about 100% by weight, about 40% to about 60% by weight, about 60% to about 100% by weight, or about 80% to about 100% by weight, based on the total weight of the core layer.
[0116] In an embodiment, the core layer of exemplary embodiment 3 may include high density polyethylene (HDPE). In one or more embodiments, the core layer may include up to 50 wt% high density polyethylene, based on the total weight of the core layer. In some embodiments, the core layer may include from about 0 wt% to about 50 wt%, from about 0 wt% to about 40 wt%, from about 0 wt% to about 20 wt%, from about 20 wt% to about 50 wt%, from about 20 wt% to about 40 wt%, or from about 40 wt% to about 50 wt% high density polyethylene, based on the total weight of the core layer.
[0117] Optionally, in some embodiments, the core layer of exemplary embodiment 3 may include low density polyethylene (LDPE). In one or more embodiments, the core layer of exemplary embodiment 3 may include less than 50 wt% low density polyethylene, based on the total weight of the core layer. In some embodiments, the core layer of exemplary embodiment 3 may include from about 0 wt% to about 50 wt%, from about 0 wt% to about 40 wt%, from about 0 wt% to about 20 wt%, from about 20 wt% to about 50 wt%, from about 20 wt% to about 40 wt%, or from about 40 wt% to about 50 wt% low density polyethylene, based on the total weight of the core layer.
[0118] The second layer, the third layer, or both of the multilayer film of exemplary embodiment 3 may each have a thickness of 0.5 micrometers (μm or micron) to 60 μm. In other embodiments, the second layer, the third layer, or both of the multilayer film of exemplary embodiment 1 may have a thickness of 0.5 μm to 50 μm, 0.5 μm to 25 μm, 0.5 μm to 10 μm, 0.5 μm to 5 μm, 0.5 μm to 1.0 μm, 1.0 μm to 50 μm, 1.0 μm to 25 μm, 1.0 μm to 10 μm, 1.0 μm to 5 μm, 5 μm to 50 μm, 5 μm to 25 μm, 5 μm to 10 μm, 10 μm to 50 μm, 10 μm to 25 μm, or 25 μm to 50 μm.
[0119] The second layer, the third layer, or both of the multilayer film of Exemplary Embodiment 3 may constitute 20% to 70% by weight of the total weight of the multilayer film of Exemplary Embodiment 3. In some embodiments, the second layer, the third layer, or both of the multilayer film of Exemplary Embodiment 1 may constitute 20% to 60% by weight, 20% to 40% by weight, 40% to 70% by weight, 40% to 60% by weight, or 60% to 70% by weight of the total weight of the multilayer film of Exemplary Embodiment 3.
[0120] In one or more embodiments, the second layer, the third layer, or both of Exemplary Embodiment 3 may each contain at least 40% by weight of the polyethylene composition of the present disclosure, based on the total weight of each layer. In some embodiments, the second layer, the third layer, or both of Exemplary Embodiment 3 may each contain from about 50% to about 100% by weight, from about 50% to about 80% by weight, from about 50% to about 60% by weight, from about 60% to about 100% by weight, from about 60% to about 80% by weight, or from about 80% to about 100% by weight of the polyethylene composition of the present disclosure, based on the total weight of each layer.
[0121] In one or more embodiments, the second layer, the third layer, or both of Exemplary Embodiment 3 may each contain less than 50% by weight of high density polyethylene, based on the total weight of each layer. In some embodiments, only one of the second layer or the third layer may contain high density polyethylene. In some embodiments, the second layer or the third layer may each contain from about 0% to about 50% by weight, from about 0% to about 40% by weight, from about 0% to about 20% by weight, from about 5% to about 50% by weight, from about 5% to about 40% by weight, from about 5% to about 20% by weight, from about 20% to about 50% by weight, from about 20% to about 40% by weight, or from about 40% to about 50% by weight of high density polyethylene, based on the total weight of each layer.
[0122] In one or more embodiments, the second layer, the third layer, or both of the exemplary embodiment 3 may contain less than 50% by weight of low-density polyethylene, based on the total weight of each layer. In some embodiments, the second layer, the third layer, or both may contain low-density polyethylene in amounts of about 5% to about 50% by weight, about 5% to about 40% by weight, about 5% to about 20% by weight, about 20% to about 50% by weight, about 20% to about 40% by weight, or about 40% to about 50% by weight, based on the total weight of each layer.
[0123] Method for producing the film described herein Various methodologies are considered for the production of multilayer films. In one or more embodiments, the process for producing a multilayer film may include extrusion of a cast film or extrusion of an inflated film.
[0124] In some embodiments, the process for producing a multilayer film may include forming inflation film bubbles. In some embodiments, the inflation film bubbles may be multilayer inflation film bubbles. According to this embodiment, the multilayer inflation film bubbles may further include at least five layers (a first layer, a second layer, a third layer, a fourth layer, and a fifth layer as described herein), and these at least five layers may be adhered to one another. In some embodiments, each of the first and fifth layers may contain linear low-density polyethylene, the second and fourth layers may contain high-density polyethylene, and the third layer may contain the polyethylene composition described herein.
[0125] In an embodiment of the inflation film process, an extruded film can be formed (inflated) from an extrusion die and pulled upward in a nip shape through a tower. The film can then be wound onto a core. Before winding the film onto the core, the ends of the film can be cut and folded using a folding device. This makes it difficult to separate the layers of film, which can be important for general transport applications or for heavy-duty transport sack applications.
[0126] In further embodiments, inflation film bubbles may be formed via an inflation film extrusion line having a length-to-diameter ("L / D") ratio of 30:1. In some embodiments, the extrusion line may have a blow-up ratio of about 1 to about 5, about 1 to about 3, about 2 to about 5, or about 2 to about 3. In some embodiments, the extrusion line may utilize a die with internal bubble cooling. In some embodiments, the die gap may be about 1 millimeter (mm) to about 5 mm, about 1 mm to about 3 mm, about 2 mm to about 5 mm, or about 2 mm to about 3 mm.
[0127] In some embodiments, the extrusion line may utilize a film thickness gauge scanner. In some embodiments, the multilayer film thickness can be maintained at approximately 15 μm to 115 μm during the extrusion process. In other embodiments, the multilayer film thickness can be maintained at approximately 15 μm to 100 μm, 15 μm to 75 μm, 15 μm to 50 μm, 15 μm to 25 μm, 25 μm to 115 μm, 25 μm to 100 μm, 25 μm to 75 μm, 25 μm to 50 μm, 50 μm to 115 μm, 50 μm to 100 μm, 50 μm to 75 μm, 75 μm to 115 μm, 75 μm to 100 μm, or 100 μm to 115 μm.
[0128] In some embodiments, the step of forming multilayer inflation film bubbles may be carried out at a temperature of 350–500°F or 375–475°F. The output speed may be approximately 5 lb / h / in to approximately 25 lb / h / in, approximately 5 lb / h / in to approximately 20 lb / h / in, approximately 5 lb / h / in to approximately 15 lb / h / in, approximately 5 lb / h / in to approximately 10 lb / h / in, approximately 10 lb / h / in to approximately 25 lb / h / in, approximately 10 lb / h / in to approximately 20 lb / h / in, approximately 10 lb / h / in to approximately 15 lb / h / in, approximately 15 lb / h / in to approximately 25 lb / h / in, approximately 15 lb / h / in to approximately 20 lb / h / in, or approximately 20 lb / h / in to approximately 25 lb / h / in.
[0129] Goods Embodiments of the present disclosure also relate to articles such as packages formed from the multilayer films of the present disclosure. Such packages can be formed from any of the multilayer films of the present disclosure as described herein. The multilayer films of the present disclosure are particularly useful in articles where good tear strength and dirt strength are desired.
[0130] Examples of such articles include flexible packaging, pouches, upright pouches, and pre-packaged packaging or pouches. In some embodiments, the multilayer films or laminates of the Disclosure can be used in sturdy transport sacks. In some embodiments, one or more of the aforementioned sturdy transport sacks can be used for transport purposes.
[0131] Various methods for producing embodiments of articles from multilayer films disclosed herein will be well known to those skilled in the art.
[0132] Polyethylene composition
[0133] (A) Composition and characterization of polyethylene In one or more embodiments, the polyethylene composition is 0.924 g / cm³ 3 ~0.936 g / cm³ 3 It may have a density of 0.924 g / cm³. For example, embodiments of the polyethylene composition of this disclosure have a density of 0.924 g / cm³. 3 ~0.931 g / cm³ 3 , 0.924 g / cm³ 3 ~0.928 g / cm³ 3 , 0.927 g / cm³ 3 ~0.931 g / cm³ 3 , or 0.929 g / cm³ 3 ~0.933g / cm 3 It may have a density of 0.924 to 0.928 g / cm³. According to additional embodiments, the polyethylene composition may have a density of 0.924 to 0.928 g / cm³. 3 ~0.932 g / cm³ 3 , 0.932 g / cm³ 3 ~0.936 g / cm³ 3 , or the density may be any combination of these ranges.
[0134] In one or more embodiments, the polyethylene composition may have a melt index (I2) of 0.25 g / 10 min to 2.0 g / 10 min, for example, 0.5 g / 10 min to 1.2 g / 10 min. For example, in one or more embodiments, the polyethylene composition may have a melt index (I2) of 0.25 g / 10 min to 0.5 g / 10 min, 0.5 g / 10 min to 0.7 g / 10 min, 0.7 g / 10 min to 0.9 g / 10 min, 0.59 g / 10 min to 1.1 g / 10 min, 1.1 g / 10 min to 1.3 g / 10 min, 1.3 g / 10 min to 1.5 g / 10 min, 1.5 g / 10 min to 1.7 g / 10 min, 1.7 g / 10 min to 2.0 g / 10 min, or any combination of these ranges. According to additional embodiments, the polyethylene composition may have a melt index (I2) of 0.65 g / 10 min to 1.05 g / 10 min.
[0135] According to the embodiments, the polyethylene composition may have a molecular weight distribution in the range of 2.5 to 8.0, expressed as the ratio of weight-average molecular weight to log-average molecular weight (Mw / Mn). For example, the polyethylene composition may have a molecular weight distribution of 2.5 to 3.0, 3.0 to 3.5, 3.5 to 4.0, 4.0 to 4.5, 4.5 to 5.0, 5.0 to 5.5, 5.5 to 6.0, 6.0 to 6.5, 6.5 to 7.0, 7.0 to 7.5, 7.5 to 8.0, or any combination of these ranges. In additional embodiments, the polyethylene composition may have a molecular weight distribution of 3.0 to 5.0. As described herein, the molecular weight distribution can be calculated according to the gel permeation chromatography (GPC) technique described herein.
[0136] According to one or more additional embodiments, the polyethylene composition may have a zero shear viscosity ratio of less than 3.0. For example, the polyethylene composition may have a zero shear viscosity ratio of less than 2.9, less than 2.8, less than 2.7, less than 2.6, less than 2.5, less than 2.4, less than 2.3, less than 2.2, less than 2.1, less than 2.0, less than 1.9, less than 1.8, less than 1.7, less than 1.6, less than 1.5, less than 1.4, less than 1.3, less than 1.2, or possibly less than 1.1. In one or more embodiments, the polyethylene composition may have a zero shear viscosity ratio of at least 1.0.
[0137] As described herein, a polyethylene “fraction” refers to a portion of the overall composition of a polyethylene composition. Embodiments of this disclosure include at least a “first polyethylene fraction” and a “second polyethylene fraction.” The various fractions contained in a polyethylene composition can be quantified by their temperature range in the elution profile via an improved comonomer composition distribution (iCCD) analysis method. Unless otherwise specified, all elution profiles referred to herein are observed via iCCD. Examples of such fractions will be better understood by considering the examples provided herein. Generally, a first fraction may contain a single peak in the temperature range of the first fraction, and a second fraction may contain a single peak in the temperature range of the second fraction. The polyethylene compositions described herein may be referred to as “multimodal,” meaning that those polyethylene compositions contain at least two peaks in their elution profile. Some embodiments may be “bimodal,” meaning that there are two main peaks.
[0138] Referring to the iCCD distribution described above, FIG. 1 schematically shows a sample iCCD distribution 100 along with a cumulative weight fraction curve 200. FIG. 1 generally shows some of the characteristics of the iCCD profile of the polyethylene compositions described herein, such as the first fraction, the second fraction, the half-peak width, etc., which are discussed in detail herein. Thus, FIG. 1 can be used as a reference with respect to the disclosure related to the iCCD profile provided herein. Specifically, a first fraction 102 and a second fraction 106 are shown. The first fraction 102 has a peak 104, and the second fraction 106 has a peak 108. Each fraction has a half-peak width 110 and 112. It should be understood that the profile of FIG. 1 is not obtained from experiments or observations, but instead is provided for the purpose of providing information to explain certain characteristics of the iCCD elution profile.
[0139] In one or more embodiments, the first polyethylene fraction may have a single peak in the temperature range of 45°C to 87°C in the elution profile via iCCD. As used herein, "single peak" refers to an iCCD in which a particular fraction contains only a single peak. That is, in some embodiments, the iCCDs of the first and second polyethylene fractions form a single peak including only an upward sloping region followed by a downward sloping region. In one or more embodiments, the single peak of the first polyethylene fraction may be in the temperature range of 60°C to 85°C, such as 70°C to 85°C. Without being bound by theory, in at least some embodiments of the polyethylene compositions of the present disclosure where a dual reactor design is used for polymerization, a combination of high density crystalline domains and low density amorphous domains may be present. Impact strength is mainly controlled by the tie concentration connecting the amorphous regions or adjacent lamellae. When the density is less than 0.910 g / cm 3 the relative tie chain concentration is presumed to be relatively large. The peak of the first polymer fraction in the compositions of the present disclosure may be in the temperature range of 60°C to 85°C, which may provide a higher tie chain concentration and result in functional benefits such as improved toughness.
[0140] It should be understood that the peaks of the first or second polyethylene fraction cannot be formed by the local minimums of each polyethylene fraction at a fixed temperature boundary. In other words, the peak must be a peak in the context of the entire range, not a peak formed by the threshold temperature of the polyethylene fraction. For example, if a polyethylene fraction has a single peak followed by a single trough (an upward slope followed by a downward slope followed by an upward slope), then such a polyethylene fraction will have only a single peak.
[0141] In one or more embodiments, the second polyethylene fraction may have a single peak in the temperature range of 95°C to 120°C in the elution profile via iCCD. The temperature range of 95°C to 120°C for the second polyethylene fraction may be desirable because the low molecular weight, high density components at 95°C to 120°C allow polyethylene to achieve a higher overall density while maintaining a lower density fraction, as described by the ratio of these two fractions.
[0142] In one or more embodiments, the width of a single peak in the second polyethylene fraction at 50 percent of the peak height may be less than 5.0°C, less than 4°C, or possibly less than 3°C. Generally, the lower temperature range at 50 percent of the peak height corresponds to a “sharper” peak. While not bound by any particular theory, “sharper” or “narrower” peaks are thought to be properties produced by molecular catalysts, indicating minimal comonomer incorporation in the high-density fraction and allowing for a greater density split between the two fractions.
[0143] In one or more embodiments, the polyethylene composition may have a minimum value in the elution profile via iCCD in the temperature range of 80°C to 90°C. This minimum value may be located between the peaks of the first polyethylene fraction and the second polyethylene fraction.
[0144] In the embodiments described herein, the first polyethylene fraction area is the area within the elution profile at 45°C to 87°C under a single peak of the first polyethylene fraction. Similarly, the second polyethylene fraction area is the area within the elution profile at 95°C to 120°C under a single peak of the second polyethylene fraction. The first polyethylene fraction area and the second polyethylene fraction can generally correspond to the total relative mass of each polymer fraction in the polyethylene composition.
[0145] According to one or more embodiments, the difference between a single peak in the second polyethylene fraction and a single peak in the first polyethylene fraction may be at least 10°C. For example, the difference between a single peak in the second polyethylene fraction and a single peak in the first polyethylene fraction may be at least 12°C, 14°C, 16°C, 18°C, or possibly at least 20°C. In general, the polyethylene fraction area in the iCCD profile can be determined by integrating the iCCD profile between a specified start temperature and an end temperature.
[0146] In one or more embodiments, the first polyethylene fraction area may constitute at least 40% of the total area of the elution profile (e.g., at least 42%, at least 44%, at least 46%, at least 48%, at least 50%, at least 52%, or possibly at least 54%) of the total area of the elution profile. For example, the first polyethylene fraction area may constitute 40% to 65% of the total area of the elution profile, e.g., 42% to 58%, 43% to 45%, 45% to 47%, 53% to 55%, or 55% to 57%.
[0147] According to one or more embodiments, the second polyethylene fraction area may constitute at least 25% of the total area of the elution profile (e.g., at least 30%, at least 35%, or possibly at least 40% of the total area of the elution profile). For example, the first polyethylene fraction area may constitute 20% to 50%, 27% to 31%, or 41% to 48% of the total area of the elution profile.
[0148] According to some embodiments, the ratio of the area of the first polyethylene fraction to the area of the second polyethylene fraction can be between 0.75 and 2.5 (e.g., 0.75 to 1.0, 1.0 to 1.25, 1.25 to 1.5, 1.5 to 1.75, 1.75 to 2.0, 2.0 to 2.25, 2.25 to 2.5, or any combination of these ranges).
[0149] In one or more embodiments, the polyethylene composition is formed by polymerization of ethylene with a comonomer such as a C3-C12 alkene. The assumed comonomers include C6-C9 alkenes such as 1-octene and 1-hexene. In one or more embodiments, the comonomer is 1-octene.
[0150] In one or more embodiments, the difference between a single peak in the second polyethylene fraction and a single peak in the first polyethylene fraction is at least 10°C, at least 12.5°C, at least 15°C, at least 17.5°C, or optionally at least 20°C.
[0151] In one or more embodiments, the first polyethylene fraction may have a melt index (I2) of 0.01 to 0.18 g / 10 min. For example, according to one or more embodiments, the first polyethylene fraction may have a melt index (I2) of 0.01 g / 10 min to 0.03 g / 10 min, 0.03 g / 10 min to 0.05 g / 10 min, 0.05 g / 10 min to 0.07 g / 10 min, 0.07 g / 10 min to 0.09 g / 10 min, 0.09 g / 10 min to 0.11 g / 10 min, 0.11 g / 10 min to 0.13 g / 10 min, 0.13 g / 10 min to 0.15 g / 10 min, 0.15 g / 10 min to 0.18 g / 10 min, or any combination of these ranges.
[0152] In one or more embodiments, the second polyethylene fraction may have a melt index (I2) of 1 to 10,000 g / 10 min. For example, in one or more embodiments, the second polyethylene fraction may have a melt index (I2) of 10 g / 10 min to 1,000 g / 10 min, 20 g / 10 min to 800 g / 10 min, 1 g / 10 min to 100 g / 10 min, 100 g / 10 min to 1,000 g / 10 min, 1,000 g / 10 min to 10,000 g / 10 min, or any combination of these ranges.
[0153] In one or more embodiments, the weight-average molecular weight of the second polyethylene fraction may be 120,000 g / mol or less, for example, 20,000 g / mol to 120,000 g / mol, or 40,000 g / mol to 65,000 g / mol. In additional embodiments, the weight-average molecular weight of the second polyethylene fraction may be 20,000 g / mol to 40,000 g / mol, 40,000 g / mol to 60,000 g / mol, 60,000 g / mol to 80,000 g / mol, 80,000 g / mol to 100,000 g / mol, 100,000 g / mol to 120,000 g / mol, or any combination of these ranges. The molecular weight of the polyethylene fraction can be calculated based on the results of GPC as described below.
[0154] The polyethylene compositions described herein may have relatively good dirt strength when formed into single-layer inflation films. According to one or more embodiments, a single-layer inflation film formed from a polyethylene composition and having a thickness of 2 mils has a dirt drop impact of at least 1000 grams when measured according to ASTM D1709 Method A. In additional embodiments, a single-layer inflation film formed from a polyethylene composition and having a thickness of 2 mils has a dirt drop impact of at least 1100 grams, at least 1200 grams, at least 1300 grams, at least 1400 grams, at least 1500 grams, at least 1600 grams, at least 1700 grams, at least 1800 grams, at least 1900 grams, or possibly at least 2000 grams when measured according to ASTM D1709 Method A.
[0155] According to additional embodiments, the polyethylene composition may have a Dow rheology index of 5 or less, for example, 4 or less, 3 or less, 2 or less, or possibly 1 or less.
[0156] In one or more embodiments, the polyethylene compositions of the present disclosure may further include additional components such as one or more additives. Such additives include, but are not limited to, antistatic agents, color enhancers, dyes, lubricants, fillers such as TiO2 or CaCO3, opacifiers, nucleating agents, processing aids, pigments, primary antioxidants, secondary antioxidants, UV stabilizers, antiblocking agents, slip agents, tackifiers, flame retardants, antimicrobial agents, odor reducers, antifungal agents, and combinations thereof. Based on the weight of the polyethylene composition containing such additives, the polyethylene composition may contain such additives in total in an amount of about 0.1 to about 10 weight percent.
[0157] (B) Polymerization Any conventional polymerization process may be used to produce the polyethylene compositions described herein. Such conventional polymerization processes include, but are not limited to, slurry polymerization processes and solution polymerization processes using one or more conventional reactors, such as loop reactors, isothermal reactors, stirred-tank reactors, simultaneous or continuous batch reactors, and / or any combination thereof. The polyethylene compositions may be produced, for example, by a solution-phase polymerization process using one or more loop reactors, isothermal reactors, and combinations thereof.
[0158] Generally, solution-phase polymerization processes can be carried out in one or more well-agitated reactors, such as one or more isothermal loop reactors or one or more adiabatic reactors, at temperatures in the range of 115–250°C (e.g., 115–210°C) and pressures in the range of 300–1,000 psi (e.g., 400–800 psi). In some embodiments, in a double reactor, the temperature of the first reactor is in the range of 115–190°C (e.g., 160–180°C) and the temperature of the second reactor is in the range of 150–250°C (e.g., 180–220°C). In other embodiments, in a single reactor, the reactor temperature is in the range of 115–250°C (e.g., 115–225°C).
[0159] The residence time in the solution-phase polymerization process can range from 2 to 30 minutes (e.g., 5 to 25 minutes). Ethylene, solvent, hydrogen, one or more catalyst systems, optionally one or more cocatalysts, and optionally one or more comonomers are continuously supplied to one or more reactors. Exemplary solvents include, but are not limited to, isoparaffins. For example, such solvents are commercially available from ExxonMobil Chemical Co., Houston, Texas, under the name ISOPAR E. The resulting mixture of the polyethylene composition and solvent is then removed from the reactor, and the polyethylene composition is isolated. The solvent is typically recovered via a solvent recovery unit, such as a heat exchanger and a gas-liquid separator drum, and then recycled back into the polymerization system.
[0160] In some embodiments, the polyethylene composition can be produced by solution polymerization in a double reactor system, such as a double-loop reactor system, in the presence of one or more catalyst systems. In some embodiments, only ethylene is polymerized. Furthermore, one or more co-catalysts may be present. In another embodiment, the polyethylene composition can be produced by solution polymerization in a single reactor system, such as a single-loop reactor system, in the presence of two catalyst systems. In some embodiments, only ethylene is polymerized.
[0161] (C) Catalyst system Specific embodiments of catalyst systems that can be used in one or more embodiments to produce the polyethylene compositions described herein are described here. It should be understood that the catalyst systems of this disclosure may be implemented in different forms and should not be construed as being limited to the specific embodiments described herein. Rather, the embodiments are provided so that this disclosure may be thorough and complete and to fully convey the scope of the subject matter to those skilled in the art.
[0162] The term "independently selected" is used in R 1 , R 2 , R 3 , R 4 , and R 5 The R groups, such as R, may be the same or different (for example, R 1 , R 2 , R 3 , R 4 , and R 5 However, all are substituted alkyl groups, or R 1 and R 2 However, it is a substituted alkyl, R 3The term R is used herein to indicate that, for example, it may be an aryl group. The use of the singular form includes the use of the plural form, and vice versa (for example, hexane solvent contains multiple hexanes). A named R group will generally have a structure that is recognized in the art as corresponding to the R group bearing that name. These definitions are intended to supplement and illustrate, and not to exclude, definitions known to those skilled in the art.
[0163] The term "procatalyst" refers to a compound that exhibits catalytic activity when combined with an activator. The term "activator" refers to a compound that chemically reacts with a procatalyst to convert it into a catalytically activated catalyst. As used herein, the terms "cocatalyst" and "activator" are interchangeable.
[0164] When used to describe a chemical group containing a specific carbon atom, "(C x ~C y The parenthetical expression in the form of ")" means that the unsubstituted form of the chemical group has x carbon atoms and y carbon atoms, including x and y. For example, (C1~C 40 ) Alkyl is an alkyl group having 1 to 40 carbon atoms in its unsubstituted form. In some embodiments and general structures, a particular chemical group is R S It may be replaced by one or more substituents such as (C x ~C y The chemical group R is defined using ) S The substitution version is any base R S Depending on the identity, it may contain more than y carbon atoms. For example, "R S Strictly speaking, one group R is phenyl (-C6H5). S Replaced by (C1~C 40 )alkyl can contain 7 to 46 carbon atoms. Therefore, generally, the parenthetical "(C x ~C y A substituent R that contains one or more carbon atoms in a chemical group defined using ) SWhen substituted by, the minimum and maximum total number of carbon atoms in the chemical group is, in both x and y, all substituents R containing carbon atoms. S It is determined by adding the sum of the carbon atoms derived from [the source].
[0165] The term "substituted" means that at least one hydrogen atom (-H) bonded to a carbon or heteroatom of the corresponding unsubstituted compound or functional group is a substituent (e.g., R S This means that all hydrogen atoms (H) bonded to the carbon or heteroatom of the corresponding unsubstituted compound or functional group are replaced by substituents (e.g., R S This means that the atoms are replaced by the substituents. The term "polysubstituted" means that at least two, but fewer than all, hydrogen atoms bonded to the carbon or heteroatom of the corresponding unsubstituted compound or functional group are replaced by the substituents.
[0166] The term "-H" refers to a hydrogen atom or hydrogen radical covalently bonded to another atom. "Hydrogen" and "-H" are interchangeable and mean the same thing unless otherwise specified.
[0167] (C1~C 40 The term "hydrocarbyl" refers to a hydrocarbon radical consisting of 1 to 40 carbon atoms. 40 The term "hydrocarbylene" means a hydrocarbon diradical having 1 to 40 carbon atoms, and each hydrocarbon radical and each hydrocarbon diradical is aromatic or non-aromatic, saturated or unsaturated, linear or branched, cyclic (monocyclic and polycyclic, condensed and non-condensed polycyclic including bicyclic, containing 3 or more carbon atoms) or acyclic, unsubstituted or with one or more R S It has been replaced by.
[0168] In this disclosure, (C1~C 40 Hydrocarbyl is either unsubstituted or substituted (C1~C 40 ) alkyl, (C3~C 40)Cycloalkyl, (C3~C 20 )Cycloalkyl-(C1~C 20 ) Alkilen, (C6~C 40 )aryl, or (C6~C 20 )aryl-(C1~C 20 ) may be alkylene. In some embodiments, the above (C1~C 40 Each of the hydrocarbyl groups has up to 20 carbon atoms (i.e., (C1~C 20 (Hydrocarbyl), in other embodiments, having up to 12 carbon atoms.
[0169] (C1~C 40 )alkyl" and "(C1~C 18 The term "alkyl" refers to an unsubstituted or one or more R atoms, each consisting of 1 to 40 carbon atoms or 1 to 18 carbon atoms. S This refers to saturated linear or branched hydrocarbon radicals that are substituted by (C1~C). 40 Examples of alkyl groups include unsubstituted (C1~C 20 ) alkyl, unsubstituted (C1~C 10 ) Alkyl, unsubstituted (C1~C5) alkyl, methyl, ethyl, 1-propyl, 2-propyl, 1-butyl, 2-butyl, 2-methylpropyl, 1,1-dimethylethyl, 1-pentyl, 1-hexyl, 1-heptyl, 1-nonyl, and 1-decyl. Substituted (C1~C 40 Examples of alkyl groups include substitutions (C1~C 20 ) alkyl, substituted (C1~C 10 ) alkyl, trifluoromethyl, and [C 45 It is alkyl. [C 45 The term ]alkyl (in square brackets) means that there are up to 45 carbon atoms in the radical, including substituents, for example, one R is (C1-C5)alkyl. S Replaced by (C 27 ~C 40 Each (C1-C5) alkyl group may be methyl, trifluoromethyl, ethyl, 1-propyl, 1-methylethyl, or 1,1-dimethylethyl.
[0170] (C6~C 40 The term "aryl" refers to a group of 6 to 40 carbon atoms that are either unsubstituted or substituted (one or more R) S (By) This refers to monocyclic, bicyclic, or tricyclic aromatic hydrocarbon radicals, of which at least 6 to 14 carbon atoms are aromatic ring carbon atoms, and monocyclic, bicyclic, or tricyclic radicals each contain 1, 2, or 3 rings, one ring is aromatic, and 2 or 3 rings are independently condensed or uncondensed, and at least one of 2 or 3 rings is aromatic. Unsubstituted (C6~C 40 Examples of aryls include unsubstituted (C6~C 20 ) Aryl, unsubstituted (C6~C 18 )aryl, 2-(C1~C5)alkylphenyl, 2,4-bis(C1~C5)alkylphenyl, phenyl, fluorenyl, tetrahydrofluorenyl, indacenyl, hexahydroindacenyl, indenyl, dihydroindenyl, naphthyl, tetrahydronaphthyl, and phenanthrene. Substitutions (C6~C 40 )Examples of aryl substitutions (C1~C 20 ) Aryl, substitution (C6~C 18 )aryl, 2,4-bis[(C 20 These are alkyl-phenyl, polyfluorophenyl, pentafluorophenyl, and fluoren-9-on-1-yl.
[0171] (C3~C 40 The term "cycloalkyl" means unsubstituted or one or more R S This refers to saturated cyclic hydrocarbon radicals of 3 to 40 carbon atoms that are substituted with (C). Other cycloalkyl groups (e.g., (C) x ~C y A cycloalkyl group has x to y carbon atoms and is either unsubstituted or has one or more R atoms. S It is defined in a similar format as either being replaced by (C3~C). 40 Examples of cycloalkyl groups include unsubstituted (C3~C) 20) Cycloalkyl, unsubstituted (C3~C 10 These are cycloalkyl, cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl, and cyclodecyl. Substitutions (C3~C 40 Examples of cycloalkyl groups include substitutions (C3~C 20 )Cycloalkyl, substituted (C3~C 10 These are cycloalkyl, cyclopentanon-2-yl, and 1-fluorocyclohexyl.
[0172] (C1~C 40 Examples of hydrocarbylenes include unsubstituted or substituted (C6~C 40 ) Alliren, (C3~C 40 )Cycloalkylenes, and (C1~C 40 ) Alkylene (for example (C1~C 20 Examples include alkylenes. In some embodiments, diradicals are located on the same carbon atom (e.g., -CH2-), on adjacent carbon atoms (i.e., 1,2-diradicals), or separated by one, two, or more intervening carbon atoms (e.g., 1,3-diradicals, 1,4-diradicals, etc.). Some diradicals include α,ω-diradicals. α,ω-diradicals are diradicals that have the largest carbon skeleton spacing between radical carbons. (C2~C 20 Some examples of alkylene α,ω-diradicals include ethane-1,2-diyl (i.e., -CH2CH2-), propane-1,3-diyl (i.e., -CH2CH2CH2-), and 2-methylpropane-1,3-diyl (i.e., -CH2CH(CH3)CH2-). (C6~C 50 Some examples of arylene α,ω-diradicals include phenyl-1,4-diyl, naphthalene-2,6-diyl, or naphthalene-3,7-diyl.
[0173] (C1~C 40 The term "alkylene" is either unsubstituted or has one or more R SThis refers to a saturated, linear, or branched diradical of 1 to 40 carbon atoms that is substituted by (i.e., the radical is not on a ring atom). Unsubstituted (C1~C 50 ) An example of alkylene is unsubstituted (C1~C 20 ) Alkylenes, including unsubstituted -CH2CH2-, -(CH2)3-, -(CH2)4-, -(CH2)5-, -(CH2)6-, -(CH2)7-, -(CH2)8-, -CH2C*HCH3, and -(CH2)4C*(H)CH3, where "C*" represents a carbon atom from which a hydrogen atom has been removed to form a secondary or tertiary alkyl radical. Substituted (C1~C 50 ) An example of alkylene is substitution (C1~C 20 ) Alkylene, -CF2-, -C(O)-, and -(CH2) 14 It is C(CH3)2(CH2)5- (i.e., 6,6-dimethyl-substituted n-1,20-eicosylene). As mentioned above, there are two R S (C1~C 18 ) Because alkylenes can be formed, substitution (C1~C 50 Examples of alkylenes include 1,2-bis(methylene)cyclopentane, 1,2-bis(methylene)cyclohexane, 2,3-bis(methylene)-7,7-dimethyl-bicyclo[2.2.1]heptane, and 2,3-bis(methylene)bicyclo[2.2.2]octane.
[0174] (C3~C 40 The term "cycloalkylene" means unsubstituted or one or more R S This refers to a cyclic diradical of 3 to 40 carbon atoms that is substituted by (i.e., the radical lies on the ring atoms).
[0175] The term "heteroatom" refers to an atom other than hydrogen or carbon. Examples of heteroatoms include O, S, S(O), S(O)2, and Si(R). C )2, P(R P ), N(R N ), -N=C(R C )2, -Ge(R C )2-, or -Si(RC )- are listed, and each R C , each R N , and each R P is non-substitutable (C1~C 18 ) Hydrocarbyl or -H. The term "heterohydrocarbon" refers to a molecule or molecular skeleton in which one or more carbon atoms are replaced by heteroatoms. (C1~C 40 The term "heterohydrocarbyl" refers to a heterohydrocarbon radical consisting of 1 to 40 carbon atoms. 40 The term "heterohydrocarbile" refers to a heterohydrocarbon diradical having 1 to 40 carbon atoms, where each heterohydrocarbon has one or more heteroatoms. Heterohydrocarbile radicals reside on carbon atoms or heteroatoms, and heterohydrocarbile diradicals may reside on (1) one or two carbon atoms, (2) one or two heteroatoms, or (3) one carbon atom and one heteroatom. Each (C1~C 50 )heterohydrocarbyl and (C1~C 50 ) Heterohydrocarbylenes are either unsubstituted or substituted (one or more R S They may be aromatic or non-aromatic, saturated or unsaturated, linear or branched, cyclic (including monocyclic and polycyclic, fused polycyclic and non-fused polycyclic) or acyclic.
[0176] (C1~C 40 ) Heterohydrocarbyls are either unsubstituted or substituted (C1~C 40 ) Heteroalkyl, (C1~C 40 ) Hydrocarbyl-O-, (C1~C 40 ) Hydrocarbyl-S-, (C1~C 40 ) Hydrocarbyl-S(O)-, (C1~C 40 )hydrocarbyl-S(O)2-, (C1~C 40 ) Hydrocarbyl-Si(R C )2-, (C1~C 40 ) Hydrocarbyl-N(R N )-, (C1~C 40 ) Hydrocarbil-P(R P )-, (C2~C 40) Heterocycloalkyl, (C2~C 19 ) Heterocycloalkyl-(C1~C 20 ) Alkilen, (C3~C 20 )Cycloalkyl-(C1~C 19 ) Heteroalkylene, (C2~C 19 ) Heterocycloalkyl-(C1~C 20 ) Heteroalkylene, (C1~C 40 ) Heteroaryl, (C1~C 19 ) Heteroaryl-(C1~C 20 ) Alkilen, (C6~C 20 )aryl-(C1~C 19 ) Heteroalkylene, or (C1~C 19 ) Heteroaryl-(C1~C 20 ) Heteroalkylenes are also acceptable.
[0177] (C4~C 40 The term "heteroaryl" refers to a total of 4 to 40 carbon atoms and 1 to 10 heteroatoms, either unsubstituted or substituted (one or more R) atoms. S (by) means monocyclic, bicyclic, or tricyclic heteroaromatic hydrocarbon radicals, where a monocyclic, bicyclic, or tricyclic radical contains one, two, or three rings, respectively, where the two or three rings are independently condensed or uncondensed, and at least one of the two or three rings is heteroaromatic. Other heteroaryl groups (e.g., (C4~C) 12 ) such as heteroaryls, (C x ~C y Heteroaryl compounds (in general) have x to y carbon atoms (such as 4 to 12 carbon atoms) and are either unsubstituted or have one or more R atoms. SIt is defined in a similar manner as being substituted by . Monocyclic heteroaromatic hydrocarbon radicals are five-membered or six-membered rings. A five-membered ring has 5 minus h carbon atoms, where h is the number of heteroatoms, which can be 1, 2, or 3, and each heteroatom can be O, S, N, or P. Examples of five-membered heteroaromatic hydrocarbon radicals include pyrrole-1-yl, pyrrole-2-yl, furan-3-yl, thiophen-2-yl, pyrazole-1-yl, isoxazole-2-yl, isothiazole-5-yl, imidazole-2-yl, oxazole-4-yl, thiazole-2-yl, 1,2,4-triazole-1-yl, 1,3,4-oxadiazole-2-yl, 1,3,4-thiadiazole-2-yl, tetrazole-1-yl, tetrazole-2-yl, and tetrazole-5-yl. A six-membered ring has 6 minus h carbon atoms, where h is the number of heteroatoms, which can be 1 or 2, and the heteroatoms can be N or P. Examples of six-membered ring heteroaromatic hydrocarbon radicals are pyridine-2-yl, pyrimidine-2-yl, and pyrazine-2-yl. Bicyclic heteroaromatic hydrocarbon radicals can be condensed 5,6- or 6,6-ring systems. Examples of condensed 5,6-ring bicyclic heteroaromatic hydrocarbon radicals include indole-1-yl and benzimidazole-1-yl. Examples of condensed 6,6-ring bicyclic heteroaromatic hydrocarbon radicals include quinoline-2-yl and isoquinoline-1-yl. Tricyclic heteroaromatic hydrocarbon radicals can be condensed 5,6,5-, 5,6,6-, 6,5,6-, or 6,6,6-ring systems. An example of a condensed 5,6,5-ring system is 1,7-dihydropyrrolo[3,2-f]indole-1-yl. An example of a condensed 5,6,6-ring system is 1H-benzo[f]indole-1-yl. An example of a condensed 6,5,6-ring system is 9H-carbazole-9-yl. An example of a condensed 6,5,6-ring system is 9H-carbazole-9-yl. An example of a condensed 6,6,6-ring system is acridine-9-yl.
[0178] The aforementioned heteroalkyls are (C1~C 50A saturated linear or branched radical may contain 1 to 50 carbon atoms and one or more heteroatoms. Similarly, a heteroalkylene may be a saturated linear or branched diradical containing 1 to 50 carbon atoms and one or more heteroatoms. Heteroatoms as defined above include Si(R C )3, Ge(R C )3, Si(R C )2, Ge(R C )2, P(R P )2, P(R P ), N(R N )2, N(R N ), N, O, OR C S, SR C It may also contain S(O) and S(O)2, and each of the heteroalkyl group and heteroalkylene group is unsubstituted or has one or more R S It is replaced by.
[0179] Unsubstituted (C2~C 40 Examples of heterocycloalkyl groups include unsubstituted (C2~C 20 ) Heterocycloalkyl, unsubstituted (C2~C 10 Examples include heterocycloalkyls, aziridin-1-yl, oxetan-2-yl, tetrahydrofuran-3-yl, pyrrolidine-1-yl, tetrahydrothiophen-S,S-dioxide-2-yl, morpholine-4-yl, 1,4-dioxan-2-yl, hexahydroazepine-4-yl, 3-oxacyclooctyl, 5-thiocyclononyl, and 2-azacyclodecyl.
[0180] The terms "halogen atom" or "halogen" refer to radicals of fluorine (F), chlorine (Cl), bromine (Br), or iodine (I). The term "halogen" refers to fluoride (F) - ), chloride (Cl - ), bromide (Br - ), or iodide (I - This refers to the anionic form of halogen atoms, such as ).
[0181] The term "saturated" means lacking carbon-carbon double bonds, carbon-carbon triple bonds, and (in heteroatom-containing groups) carbon-nitrogen, carbon-phosphorus, and carbon-silicon double bonds. A saturated chemical group has one or more substituents R S If substituted with, one or more double and / or triple bonds may optionally have substituent R S It may or may not be present. The term "unsaturated" means containing one or more carbon-carbon double bonds, carbon-carbon triple bonds, and carbon-nitrogen, carbon-phosphorus, and carbon-silicon double bonds (in heteroatom-containing groups), provided that substituent R is present if present. S This means that it does not include any double bonds that may be present in it, or that, if present, may be present in the (hetero)aromatic ring.
[0182] According to some embodiments, the catalyst system for producing the polyethylene composition comprises a metal-ligand complex according to the following formula (I). [ka]
[0183] In formula (I), M is a metal selected from titanium, zirconium, or hafnium, the metal is in a formal oxidation state of +2, +3, or +4, n is 0, 1, or 2, when n is 1, X is a monodentate or bidentate ligand, when n is 2, each X is a monodentate ligand and is either the same or different, the metal-ligand complex as a whole is electrically neutral, and each Z is independently -O-, -S-, or -N(R) N )-, or -P(R P )- is selected from, and L is (C1~C 40 ) Hydrocarbylene or (C1~C 40 ) is a heterohydrocarbylene, (C1~C 40 ) Hydrocarbylene has a portion containing a linker skeleton of 1 to 10 carbon atoms (to which L is bonded) that links the two Z groups of formula (I), or (C1 to C 40) Heterohydrocarbylene has a portion containing a linker skeleton of 1 to 10 atoms that connects two Z groups of formula (I), (C1 to C 40 Each of the 1 to 10 atoms in the linker skeleton of heterohydrocarbylene is independently a carbon atom or a heteroatom, and each heteroatom is independently O, S, S(O), S(O)2, Si(R) C )2, Ge(R C )2, P(R C ), or N(R C ) and each R C However, independently (C1~C 30 ) Hydrocarbil or (C1~C 30 ) is a heterohydrocarbyl, R 1 and R 8 However, independently, -H, (C1~C 40 ) Hydrocarbyl, (C1~C 40 ) Heterohydrocarbyl, -Si(R C )3, -Ge(R C )3, -P(R P )2, -N(R N )2, -OR C , -SR C -NO2, -CN, -CF3, R C S(O)-, R C S(O)2-, (R C )2C=N-, R C C(O)O-, R C OC(O)-, R C C(O)N(R N )-, (R N ) Selected from the group consisting of 2NC(O)-, halogens, and radicals having the following formulas (II), (III), or (IV). [ka]
[0184] In equations (II), (III), and (IV), R 31~35 , R 41~48 , or R 51~59 Each of these is independent (C1~C 40 ) Hydrocarbyl, (C1~C 40) Heterohydrocarbyl, -Si(R C )3, -Ge(R C )3, -P(R P )2, -N(R N )2, -N=CHR C , -OR C , -SR C -NO2, -CN, -CF3, R C S(O)-, R C S(O)2-, (R C )2C=N-, R C C(O)O-, R C OC(O)-, R C C(O)N(R N )-, (R N ) Selected from 2NC(O)-, halogen, or -H, however, R 1 or R 8 The condition is that at least one of them is a radical having formula (II), formula (III), or formula (IV).
[0185] In equation (I), R 2~4 , R 5~7 , and R 9~16 Each of these is independent (C1~C 40 ) Hydrocarbyl, (C1~C 40 ) Heterohydrocarbyl, -Si(R C )3, -Ge(R C )3, -P(R P )2, -N(R N )2, -N=CHR C , -OR C , -SR C -NO2, -CN, -CF3, R C S(O)-, R C S(O)2-, (R C )2C=N-, R C C(O)O-, R C OC(O)-, R C C(O)N(R N )-, (R C ) Selected from 2NC(O)-, halogen, and -H.
[0186] In some embodiments, the polyethylene composition is formed using a first catalyst according to formula (I) in a first reactor and a different catalyst according to formula (I) in a second reactor.
[0187] In one exemplary embodiment in which a double-loop reactor is used, the pro-catalyst used in the first loop is zirconium, [[2,2'''-[[bis[1-methylethyl)germylene]bis(methyleneoxy-κO)]bis[3'',5,5''-tris(1,1-dimethylethyl)-5'-octyl[1,1':3',1''-terphenyl]-2'-orato-κO]](2-)]dimethyl-, with chemical formula C 86 H 128 It has F2GeO4Zr and the following structure (V). [ka]
[0188] In such embodiments, the procatalyst used in the second loop is zirconium, [[2,2'''-[1,3-propanediylbis(oxy-κO)]bis[3-[2,7-bis(1,1-dimethylethyl)-9H-carbazole-9-yl]]-5'-(dimethyloctylsilyl)-3'-methyl-5-(1,1,3,3-tetramethylbutyl)[1,1]-biphenyl]-2-orato-κO]](2-)]dimethyl, with chemical formula C 107 H 154 It has N2O4Si2Zr and the following structure (VI). [ka]
[0189] (D) Cocatalyst component A catalyst system comprising the metal-ligand complex of formula (I) can be catalytically activated by any technique known in the art for activating metal catalysts in olefin polymerization reactions. For example, a system comprising the metal-ligand complex of formula (I) can be catalytically activated by contacting the complex with an activating cocatalyst or by combining the complex with an activating cocatalyst. Suitable activating cocatalysts for use in the present invention include alkylaluminum, polymer or oligomeric aluminoxanes (also known as aluminoxanes), neutral Lewis acids, and nonpolymeric, non-coordinating, ion-forming compounds (including the use of such compounds under oxidizing conditions). A suitable activation technique is bulk electrolysis. Combinations of one or more of the aforementioned activating cocatalysts and techniques are also intended. The term "alkylaluminum" means monoalkylaluminum dihydride or monoalkylaluminum dihalide, dialkylaluminum hydride or dialkylaluminum halide, or trialkylaluminum. Examples of polymeric or oligomeric aluminumoxanes include methyl aluminumoxane, triisobutylaluminum-modified methyl aluminumoxane, and isobutyl aluminumoxane.
[0190] The Lewis acid activator (cocatalyst) is as described herein, comprising 1 to 3 (C1 to C 20 )Includes a group 13 metal compound containing a hydrocarbyl substituent.In one embodiment, the group 13 metal compound is tri((C1~C 20 )hydrocarbyl) substituted aluminum or tri((C1~C 20 The (hydrocarbyl)-boron compound is a tri(hydrocarbyl)-substituted aluminum, tri((C1~C 20 (hydrocarbyl)-boron compounds, tri((C1~C 10 )Alkyl) Aluminum, Tri((C6~C 18These are tris((C1-C))boron compounds and their halogenated (including perhalated) derivatives. In further embodiments, the Group 13 metal compounds are tris(fluorosubstituted phenyl)borane and tris(pentafluorophenyl)borane. In some embodiments, the activated cocatalyst is tris((C1-C) 20 ) Hydrocarbyl borate (e.g., trityltetrafluoroborate) or tri((C1~C 20 ) Hydrocarbyl ammonium tetra((C1~C 20 (Hydrocarbyl)borane (e.g., bis(octadecyl)methylammoniumtetrakis(pentafluorophenyl)borane). As used herein, the term "ammonium" means ((C1-C 20 ) Hydrocarbyl 4N + , ((C1~C 20 ) Hydrocarbyl 3N(H) + , ((C1~C 20 )hydrocarbyl)2N(H)2 + , (C1~C 20 ) Hydrocarbyl N(H)3 + , or N(H)4 + This refers to nitrogen cations, and each (C1~C 20 ) If two or more hydrocarbyl molecules are present, they may be the same or different.
[0191] As for combinations of neutral Lewis acid activators (cocatalysts), tri((C1~C4)alkyl)aluminum and halogenated tri((C6~C 18Examples include mixtures containing aryl)boron compounds, particularly combinations with tris(pentafluorophenyl)borane. Other embodiments include combinations of such neutral Lewis acid mixtures with polymers or oligomeric almoxanes, and combinations of a single neutral Lewis acid, particularly tris(pentafluorophenyl)borane, with polymers or oligomeric almoxanes. The molar ratio of (metal-ligand complex):(tris(pentafluorophenylborane):(almoxane)[e.g., (Group 4 metal-ligand complex):(tris(pentafluorophenylborane):(almoxane)] is 1:1:1 to 1:10:30, and in other embodiments, 1:1:1.5 to 1:5:10.
[0192] An activated catalyst composition can be formed by activating a catalyst system containing a metal-ligand complex of formula (I) and combining it with one or more cocatalysts, such as cation-forming cocatalysts, strong Lewis acids, or combinations thereof. Suitable activated cocatalysts include polymers or oligomeric aluminoxanes, particularly methyl aluminoxanes, as well as inert, compatible, non-coordinating, and ion-forming compounds. Exemplary suitable cocatalysts include modified methyl aluminoxane (MMAO), bis(hydrogenated tallow alkyl)methyl, and tetrakis(pentafluorophenyl)borate (1 - Examples include, but are not limited to, amines and combinations thereof.
[0193] In some embodiments, one or more of the aforementioned activated cocatalysts are used in combination with each other. Particularly preferred combinations are tri((C1-C4)hydrocarbyl)aluminum, tri((C1-C4)hydrocarbyl)borane, or a mixture of ammonium borate with an oligomer or polymeric almoxane compound. The ratio of the total number of moles of one or more metal-ligand complexes of formula (I) to the total number of moles of one or more activated cocatalysts is 1:10,000 to 100:1. In some embodiments, this ratio is at least 1:5000, in some other embodiments at least 1:1000 and 10:1 or less, and in some other embodiments 1:1 or less. When an almoxane is used alone as an activated cocatalyst, preferably the number of moles of almoxane used is at least 100 times the number of moles of the metal-ligand complex of formula (I). When tris(pentafluorophenyl)borane is used alone as an activating cocatalyst, in some other embodiments, the number of moles of tris(pentafluorophenyl)borane used relative to the total number of moles of one or more metal-ligand complexes of formula (I) is 0.5:1 to 10:1, 1:1 to 6:1, or 1:1 to 5:1. The remaining activating cocatalyst is generally used in a molar amount approximately equal to the total number of moles of one or more metal-ligand complexes of formula (I).
[0194] Test method The test methods include the following:
[0195] Melt Index Melt index I2 (or I2) and I 10(or I10) were measured according to ASTM D-1238 (Method B) at 190°C and loads of 2.16 kg and 10 kg, respectively. Their values are reported in g / 10 min. Fractions of polymer samples are measured by collecting the product polymer from the reactor that produces that particular fraction or portion of the polymer composition. For example, the first polyethylene fraction can be collected from the reactor that produces a lower density, higher molecular weight component of the polymer composition. The polymer solution is dried under vacuum before melt index measurement.
[0196] density Samples for density measurement were prepared according to ASTM D4703. Measurements were taken within one hour of sample pressurization, according to ASTM D792, Method B.
[0197] ASTM D1709 Dirt Drop The film dart drop test determines the energy required for a free-falling dart to cause a plastic film to break under specified conditions. The test result is expressed as the energy of the projectile falling from a specified height that would cause 50% of the test specimen to break.
[0198] After the film was produced, it was acclimatized for at least 40 hours at 23°C (+ / -2°C) and 50% RH (+ / -5) according to ASTM standards. The standard test conditions are 23°C (+ / -2°C) and 50% RH (+ / -5) according to ASTM standards.
[0199] The test results may be reported by either Method A, which uses a 1.5-inch diameter dart head and a 26-inch drop height, or Method B, which uses a 2.0-inch diameter dart head and a 60-inch drop height. The thickness of the specimen is measured at the center of the specimen, and the specimen is then secured in an annular specimen holder with an inner diameter of 5 inches. The dart is loaded above the center of the specimen and released by either a pneumatic or electromagnetic mechanism.
[0200] The test is conducted according to the "staircase" method. If a sample fails, a new sample is tested with the dart weight reduced by a known fixed amount. If a sample does not fail, a new sample is tested with the dart weight increased by a known amount. After 20 test specimens have been tested, the number of failures is determined. If this number is 10, the test is completed. If this number is less than 10, the test is continued until 10 failures are recorded. If this number is greater than 10, the test is continued until the total number of non-failures is 10. The dart drop strength was determined from these data, expressed in grams as a Type A dart drop impact according to ASTM D1709. All samples analyzed were 2 mils thick.
[0201] Instrumented Dirt Impact The instrumented dirt impact test is performed on plastic film specimens using an Instron CEAST 9350 impact tester, in accordance with ASTM D7192. The test is conducted using a 12.7 mm diameter tap with a hemispherical head and a 75 mm diameter clamp assembly with rubber grips. The instrument is equipped with an environmental chamber for testing at low or high temperatures. Typical specimen size is 125 mm × 125 mm. Standard test speed is 200 m / min. Film thickness is 2 mil.
[0202] Creep-zero shear viscosity measurement method Zero shear viscosity is obtained by creep testing using an AR-G2 stress-controlled rheometer (TA Instruments, New Castle, Del.) at 190°C with parallel plates of 25 mm diameter. Before zeroing the mounting fixture, the rheometer oven is set to the test temperature for at least 30 minutes. At that test temperature, the compression-molded sample disc is inserted between the plates and equilibrated for 5 minutes. The upper plate is then lowered 50 μm above the desired test gap (1.5 mm). Any excess material is trimmed and removed, and the upper plate is lowered to the desired gap. Measurements are performed under nitrogen purging at a flow rate of 5 L / min. The default creep time is set to 2 hours.
[0203] To ensure that the steady-state shear rate is low enough to be in the Newtonian region, a constant low shear stress of 20 Pa is applied to all samples. The resulting steady-state shear rate for the samples in this test is 10 -3 ~10 -4 s -1 It is within the range. The steady state is determined by taking a linear regression for all data within the last 10% time window of the plot of log(J(t)) versus log(t) (where J(t) is creep compliance and t is creep time). If the slope of the linear regression is greater than 0.97, it is considered that the steady state has been reached, and the creep test is then stopped. In all cases of this test, the slope meets the criterion within 2 hours. The steady state shear rate is determined from the slope of the linear regression for all data points within the last 10% time window of the plot of ε versus t (where ε is strain). The zero shear viscosity is determined from the ratio of the applied stress to the steady state shear rate.
[0204] To determine whether the sample deteriorates during the creep test, small-amplitude vibration shear tests are performed on the same sample before and after the creep test at 0.1–100 rad / second. The complex viscosity values of the two tests are compared. If the difference in viscosity values at 0.1 rad / second is greater than 5%, the sample is considered to have deteriorated during the creep test, and the results are discarded.
[0205] Gel permeation chromatography (GPC) The chromatography system consisted of a PolymerChar GPC-IR (Valencia, Spain) high-temperature GPC chromatograph equipped with an internal IR5 infrared detector (IR5). The autosampler oven compartment was set to 160°C, and the column compartment to 150°C. The columns used were four Agilent "Mixed A" 30 cm 20 micron linear mixed-bed columns and a 20 μm pre-column. The chromatography solvent used was 1,2,4-trichlorobenzene, which contained 200 ppm butylated hydroxytoluene (BHT). The solvent source was nitrogen-spurged. The injection volume used was 200 microliters, and the flow rate was 1.0 ml / min.
[0206] The GPC column set was calibrated using 21 polystyrene standards with narrow molecular weight distributions ranging from 580 to 8,400,000, arranged in six "cocktail" mixtures with at least a 10-fold gap between individual molecular weights. The standards were purchased from Agilent Technologies. Polystyrene standards were prepared at 0.025 grams in 50 ml of solvent for molecular weights greater than 1,000,000, and at 0.05 grams in 50 ml of solvent for molecular weights less than 1,000,000. The polystyrene standards were dissolved at 80 degrees Celsius for 30 minutes with gentle stirring. The peak molecular weights of the polystyrene standards were converted to polyethylene molecular weights using Formula 1 (as described in Williams and Ward, J. Polym. Sci., Polym. Let., 6, 621 (1968)). M ポリエチレン =A × (M ポリスチレン ) B (EQ1) In the formula, M is the molecular weight, A has a value of 0.4315, and B is equal to 1.0.
[0207] A quintic polynomial was used to fit the equivalent calibration points for each polyethylene. A slight adjustment (approximately 0.375 to 0.445) was made for A to correct the column resolution and band expansion effect so that the linear homopolymer polyethylene standard material could be obtained at 120,000 Mw.
[0208] The total plate count of the GPC column set was performed using decane (prepared with 0.04 g in 50 ml of TCB and dissolved for 20 minutes with gentle agitation). Plate count (Equation 2) and symmetry (Equation 3) were measured by 200 microliter injections according to the following formulas.
number
number
[0209] The sample was prepared semi-automatically using PolymerChar "Instrument Control" software, with a target weight of 2 mg / ml. The solvent (containing 200 ppm BHT) was added to a pre-nitrogen-spared vial with a septum cap via a PolymerChar high-temperature autosampler. The sample was dissolved at 160 degrees Celsius for 2 hours with "low-speed" shaking.
[0210] Mn (GPC) , Mw (GPC) , and Mz(GPC) The calculations were performed based on GPC results using the PolymerChar GPCOne™ software, the IR chromatogram with the baseline subtracted at each equally spaced data retrieval point (i), and the polyethylene equivalent molecular weight obtained from the narrow standard calibration curve at point (i) in Equation 1, using the internal IR5 detector (measurement channel) of the PolymerChar GPC-IR chromatograph according to Equations 4-6.
number
number
number
[0211] To monitor deviations over time, a flow rate marker (decane) was introduced into each sample via a micropump controlled by the PolymerChar GPC-IR system. This flow rate marker (FM) was used to linearly calibrate the pump flow rate (apparent flow rate) for each sample by matching the RV of each decane peak (RV(FM sample)) in the sample with that of the decane peak in the narrow standard calibration (RV(FM calibrated)). Thus, any change in the decane marker peak over time is presumed to be related to a linear shift in the flow rate (effective flow rate) throughout the run. To facilitate the highest accuracy of RV measurement of the flow rate marker peak, a least-squares fitting routine was used to fit the peaks of the flow rate marker concentration chromatogram to a quadratic equation. The first derivative of the quadratic equation was then used to determine the true peak position. After calibrating the system based on the flow rate marker peaks, the effective flow rate (relative to the narrow standard calibration) was calculated as shown in Equation 7. Processing of the flow rate marker peaks was performed using PolymerChar GPCOne® software. In an acceptable flow correction, the effective flow rate should be within + / - 0.5% of the apparent flow rate. Effective flow rate = Apparent flow rate × (RV (FM calibrated) / RV (FM sample)) (EQ7)
[0212] Improved comonomer content analysis method (iCCD) An improved comonomer content analysis method (iCCD) was developed in 2015 (Cong and Parrott et al., WO2017 / 040127A1). The iCCD test was performed using a crystallization elution fractionation instrument (CEF) (PolymerChar, Spain) equipped with an IR-5 detector (PolymerChar, Spain) and a two-angle light scattering detector Model 2040 (Precision Detectors, now Agilent Technologies). A guard column, consisting of 5 cm or 10 cm (length) × 1 / 4 inch (ID) stainless steel packed with 20-27 micron glass (MoSCi Corporation, USA), was placed directly in front of the IR-5 detector in the detector oven. Orthodichlorobenzene (ODCB, 99% anhydrous or technical grade) was used. Silica gel 40 (particle size 0.2-0.5 mm, catalog no. 10181-3) was obtained from EMD Chemicals (it can be used to pre-dry the ODCB solvent). The CEF instrument was equipped with an autosampler with N2 purging capability. Before use, dry nitrogen (N2) was sprayed onto the ODCB for 1 hour. Sample preparation was performed using the autosampler at 4 mg / mL (unless otherwise specified) while shaking at 160°C for 1 hour. The injection volume was 300 μl. The iCCD temperature profile consisted of crystallization from 105°C to 30°C at 3°C / min, thermal equilibrium at 30°C for 2 minutes (including setting the soluble fraction elution time to 2 minutes), and elution from 30°C to 140°C at 3°C / min. The flow rate during crystallization was 0.0 ml / min. The flow rate during elution was 0.50 ml / min. Data was collected at 1 data point / second.
[0213] The iCCD column was packed with gold-coated nickel particles (Bright 7GNM8-NiS, Nippon Chemical Industrial Co.) in a 15 cm (length) × 1 / 4 inch (ID) stainless steel tube. Column packing and acclimatization were performed using the slurry method according to the reference (Cong, R., Parrott, A., Hollis, C., Cheatham, M. WO2017 / 040127A1). The final pressure, including packing with TCB slurry, was 150 bar.
[0214] Column temperature calibration is performed using linear homopolymer polyethylene (CO2) as the reference material in the ODCB (comonomer content zero, melt index (I2) 1.0, polydispersity M). w / M n Conventional gel permeation chromatography was performed using a mixture of approximately 2.6 mg (1.0 mg / ml) and eicosane (2 mg / ml). iCCD temperature calibration consisted of the following four steps: (1) calculating the delay volume, which is defined as the temperature offset between the measured peak elution temperatures of eicosane minus 30.00°C; and (2) subtracting the temperature offset of the elution temperature from the iCCD raw temperature data. It should be noted that this temperature offset is a function of experimental conditions such as elution temperature and elution flow rate. (3) A linear reference curve is constructed that converts the elution temperature over the range of 30.00°C to 140.00°C such that the linear homopolymer polyethylene reference has a peak temperature of 101.0°C and eicosane has a peak temperature of 30.0°C. (4) For soluble fractions measured isothermally at 30°C, elution temperatures below 30.0°C are linearly extrapolated by using an elution heating rate of 3°C / min according to the reference material (Cerk and Cong et al., US9,688,795).
[0215] The comonomer content versus iCCD elution temperature was constructed using 12 reference substances (ethylene homopolymers and ethylene-octene random copolymers prepared with single-site metallocene catalysts, having weight-average molecular weights of ethylene equivalents ranging from 35,000 to 128,000). All of these reference substances were analyzed at 4 mg / mL using the same method as previously specified. The reported elution peak temperatures were linearly fitted to the linear equation y = -6.3515x + 101.00, where y represents the elution temperature of iCCD, x represents the octene mole%, and R 2 The value was 0.978.
[0216] The molecular weights of the polymer and polymer fractions were determined directly from an LS detector (90-degree angle) and a concentration detector (IR-5) according to the Rayleigh-Gans-Debys approximation (Striegel and Yau, Modern Size Exclusion Liquid Chromatography, pages 242 and 263), by assuming a form factor of 1 and zero virial coefficients. An integration window was set to integrate all chromatograms at elution temperatures in the range of 23.0–120°C (temperature calibration specified above).
[0217] The calculation of molecular weight (Mw) from iCCD involves the following four steps: (1) Measure the inter-detector offset. The offset is defined as the geometric volume offset between the LS detectors relative to the concentration detector. This is calculated as the difference in the elution volume (mL) of the polymer peak between the concentration detector and the LS chromatogram. This is converted to a temperature offset by using the elution thermal rate and elution flow rate. Linear high-density polyethylene (comonomer content zero, melt index (I2) 1.0, polydispersity M w / M nConventional gel permeation chromatography (iCCD) is used (approximately 2.6). The same experimental conditions as the standard iCCD method described above are used, except for the following parameters: crystallization from 140°C to 137°C at 10°C / min, thermal equilibrium time of 1 minute for soluble fraction elution at 137°C, soluble fraction (SF) time of 7 minutes, and elution from 137°C to 142°C at 3°C / min. The flow rate during crystallization is 0.0 mL / min. The flow rate during elution is 0.80 mL / min. The sample concentration is 1.0 mg / mL. (2) Shift each LS data point in the LS chromatogram to correct the inter-detector offset before integration. (3) The baseline-subtracted LS and concentration chromatogram are integrated over the entire elution temperature range of step (1). The MW detector constant is calculated using the area ratio of the LS and concentration integrated signals for HDPE samples with known MW in the range of 100,000 to 140,000 Mw. (4) The Mw of the polymer was calculated using the ratio of the integrated light scattering detector (90-degree angle) and the concentration detector, and using the MW detector constant.
[0218] The calculation of the full width at half maximum is defined as the temperature difference between the front temperature and the rear temperature at half the maximum peak height. The front temperature at half the maximum peak height is searched forward from 35.0°C, and the rear temperature at half the maximum peak height is searched backward from 119.0°C.
[0219] Zero shear viscosity ratio (ZSVR) ZSVR is defined as the ratio of the zero shear viscosity (ZSV) of a branched polyethylene material to the ZSV of a linear polyethylene material in terms of equivalent weight-average molecular weight (Mw-gpc), according to the following equations (EQ)10 and 11.
number
number
[0220] The ZSV value is obtained from a creep test at 190°C using the method described above. The Mw-gpc value is determined by the conventional GPC method (Equation 5 in the explanation of the conventional GPC method). The correlation between the ZSV of linear polyethylene and its Mw-gpc was established based on a series of linear polyethylene reference materials. An explanation of the ZSV-Mw relationship can be found in the ANTEC abstract: Karjala, Teresa P., Sammler, Robert L., Mangnus, Marc A., Hazlitt, Lonnie G., Johnson, Mark S., Hagen, Charles M.Jr., Huang, Joe WL, Reichek, Kenneth N., “Detection of low levels of long-chain branching in polyolefins”, Annual Technical Conference-Society of Plastics Engineers (2008), 66th, 887-891.
[0221] MD tear MD tear was measured according to ASTM D-1922. The force in grams required to propagate the tear across the film specimen was measured using an Elmendorf tear tester. Acting on by gravity, the pendulum oscillates in an arc, tearing the specimen through a pre-cut slit. The tear is propagated in a cross direction. The specimen is acclimatized at the pre-test temperature for a minimum of 40 hours.
[0222] Dynamic rheology analysis To characterize the rheological behavior of substantially linear ethylene polymers, S. Lai and G.W. Knight (ANTEC '93 Proceedings, Insite™ Technology Polyolefins (ITP) - New Rules in the Structure / Rheology Relationship of Ethylene & ethylene Copolymers, New Orleans, La., May 1993) introduced a new rheological measure, the Dow rheological index (DRI), which represents the "normalized relaxation time as a result of long-chain branching" of the polymer. S. Lai et al. (ANTEC'94, Dow Rheology Index (DRI) for Insite™ Technology Polyolefins (ITP): Unique structure-Processing Relationships, pp. 1814-1815) defined the DRI as the degree to which the rheology of ethylene-octene copolymers known as ITP (Dow's Insite Technology Polyolefins), which incorporate long-chain branching into their polymer backbone, deviates from the rheology of conventional linear homogeneous polyolefins, which are reported to lack long-chain branching (LCB), according to the following normalized formula. DRI = [3650000X(τ0 / η0)-1] / 10 In the equation, τ0 is the characteristic relaxation time for this material and is the zero-shear rate complex viscosity of this material. The DRI is calculated by the least-squares fitting of the rheology curve (dynamic complex viscosity η*(ω) versus applicable frequency (ω), e.g., 0.01 to 100 rad / sec) using the following generalized cross equation, as described in U.S. Patent No. 6,114,486. η*(ω)=η0 / [1+(ω·τ0)] n ] In the formula, n is the power law exponent of the material, and η*(ω) and ω are the measured complex viscosity and applied frequency data, respectively.
[0223] Dynamic rheological measurements are performed in a dynamic rheometer (e.g., TA Instruments' ARES rheometer) with 25 mm diameter parallel plates in dynamic mode under an inert atmosphere, according to ASTM D4440. In all experiments, the rheometer is thermally stabilized at 190°C for at least 30 minutes, after which the properly stabilized (with antioxidants) and compression-molded sample is inserted into the parallel plates. The plates are then closed with a positive normal force recorded on the meter to ensure good contact. After about 5 minutes at 190°C, the plates are lightly compressed and excess polymer around the plates is trimmed. It is left for another 10 minutes until thermal stability and normal force return to zero. In other words, all measurements are performed after the sample has been equilibrated at 190°C for about 15 minutes and under a complete nitrogen blanket.
[0224] Two strain sweep (SS) experiments are first performed at 190°C to determine the linear viscoelastic strain that produces a torque signal greater than 10% of the lower scale of the transducer over the entire frequency range (e.g., 0.01–100 rad / sec). The first SS experiment is performed at a low application frequency of 0.1 rad / sec. This test is used to determine the sensitivity of the torque at low frequencies. The second SS experiment is performed at a high application frequency of 100 rad / sec. This is to ensure that the selected application strain falls well within the linear viscoelastic region of the polymer so that the vibrational rheology measurements do not cause structural changes in the polymer during the test. Furthermore, a time sweep (TS) experiment is performed at a low application frequency of 0.1 rad / sec with the selected strain (determined by the SS experiment) to confirm the stability of the sample during the test.
[0225] The values of the storage (or elastic) coefficient, loss (or viscosity) coefficient (G"), complex coefficient (G*), complex viscosity (η*), and tanδ (the ratio of the loss coefficient to the storage coefficient G'VG') were obtained as a function of frequency (ω) at a given temperature (e.g., 190°C).
[0226] ASTM D882 MD and CD, 1% and 2% secant coefficients The MD (machine direction) and CD (cross direction) secant coefficients of the film were determined according to ASTM D882. The reported secant coefficient values were the average of five measurements.
[0227] Puncture strength The puncture test determines the film's resistance to probe penetration at a standard low speed, single test speed. The puncture test method is based on ASTM D5748. After film formation, the film was acclimatized for at least 40 hours at 23°C (+ / -2°C) and 50%RH (+ / -5) according to ASTM standards. Standard test conditions are 23°C (+ / -2°C) and 50%RH (+ / -5) according to ASTM standards. Puncture was measured using a tensile testing machine. Square test specimens were cut from the sheet to a size of "6 inches x 6 inches". The specimens were fixed in a "4-inch diameter" circular specimen holder, and the puncture probe was pressed into the center of the fixed film at a crosshead speed of 10 inches / minute. The internal test method conforms to ASTM D5748 with one modification. This method differed from the ASTM D5748 method in that the probe used was a 0.5-inch diameter polished steel ball on a 0.25-inch support, rather than the 0.75-inch diameter pear-shaped probe specified in D5748.
[0228] A maximum travel length of 7.7 inches was used to prevent damage to the test fixture. There was no gauge length, and before testing, the probe was brought as close as possible to the specimen without contact. A single thickness measurement was taken at the center of the specimen. For each specimen, the maximum force, force at fracture, penetration distance, and energy to fracture were determined. A total of five specimens were tested to determine the average puncture value. The puncture probe was cleaned with Kimwipes after each specimen. [Examples]
[0229] The following examples illustrate the features of the disclosure and are not intended to limit the scope of the disclosure. The performance of embodiments of the multilayer films described herein was analyzed in the following experiments.
[0230] Example 1A: Preparation of polyethylene compositions 1-5 Polyethylene compositions 1 to 5, described according to one or more embodiments for carrying out the invention, were prepared by the following methods and using the catalysts and reactors described below.
[0231] Before being introduced into the reaction environment, all raw materials (monomers and comonomers) and process solvent (high-purity isoparaffinic solvent with a narrow boiling point range, Isopar-E) are purified using molecular sieves. Hydrogen is supplied under pressure as high-purity grade and is not further purified. The reactor monomer feed stream is pressurized to over the reaction pressure via a mechanical compressor. The solvent and comonomer feed streams are pressurized to over the reaction pressure via pumps. Individual catalyst components are manually batch-diluted in the purified solvent and pressurized to over the reaction pressure. All reaction feed streams are measured using mass flowmeters and independently controlled by a computer-automated valve control system.
[0232] As shown in Figure 3, two reactor systems are used in a series configuration. Each continuous solution polymerization reactor consists of a liquid-filled, non-adiabatic, isothermal circulating loop reactor that replicates a continuous stirred tank reactor (CSTR) with heat removal. All fresh solvent, monomer, comonomer, hydrogen, and catalyst component feeds are independently controlled. The total fresh feed streams to each reactor (solvent, monomer, comonomer, and hydrogen) are temperature-controlled to maintain a single solution phase by passing the feed streams through a heat exchanger. The total fresh feed to each polymerization reactor is injected into the reactor at two locations, with approximately equal reactor volumes between each injection point. The fresh feed is controlled so that each injector accepts half of the total fresh feed flow rate. Catalyst components are injected into the polymerization reactor through injection needles. The main catalyst component feed is computer-controlled to maintain monomer conversion in each reactor at a specific target. Co-catalyst components are supplied based on a calculated specific molar ratio to the main catalyst component. Immediately after the injection point of each reactor feed, the feed stream is mixed with the contents of a circulating polymerization reactor having a static mixing element. The contents of each reactor are passed through a heat exchanger, which plays a role in removing most of the reaction heat, and the coolant side temperature plays a role in maintaining an isothermal reaction environment at a specific temperature, and are continuously circulated. Circulation around each reactor loop is provided by a pump.
[0233] In a double series reactor configuration, the effluent from the first polymerization reactor (containing solvent, monomer, comonomer, hydrogen, catalyst components, and polymer) exits the first reactor loop and is added to the second reactor loop.
[0234] The second reactor effluent enters a zone where the effluent is deactivated by the addition and reaction with a suitable reagent (water). At this same reactor outlet, other additives are added for polymer stabilization (typical antioxidants suitable for stabilization during extrusion and film production, such as octadecyl 3,5-di-Tert-butyl-4-hydroxyhydrocinnamate, tetrakis(methylene(3,5-di-Tert-butyl-4-hydroxyhydrocinnamate))methane, and tris(2,4-di-Tert-butyl-phenyl)phosphite).
[0235] Following catalyst deactivation and additive addition, the reactor effluent enters a devolving system where the polymer is removed from the non-polymer stream. The isolated polymer molten material is pelletized and collected. The non-polymer stream passes through various instruments that separate most of the ethylene removed from the system. Most of the solvent and unreacted comonomers are recycled back into the reactor after passing through a purification system. Small amounts of solvent and comonomers are purged from the process.
[0236] The reactor flow feed data flow corresponding to the values in Table 1, used to generate the examples, is schematically illustrated in Figure 3. The data is presented to account for the complexity of the solvent recirculation system and to make the reaction system easier to handle as a through-flow diagram. Table 1B shows the catalysts referenced in Table 1A. [Table 1-1] [Table 1-2] [Table 2]
[0237] Example 1B: Preparation of polyethylene composition 6 Polyethylene compositions 6 and 7, described according to one or more embodiments for carrying out the invention, were prepared by the following methods and using the catalysts and reactors described below.
[0238] Before being introduced into the reaction environment, all raw materials (monomers and comonomers) and process solvent (high-purity isoparaffinic solvent with a narrow boiling point range, Isopar-E) are purified using molecular sieves. Hydrogen is supplied under pressure as high-purity grade and is not further purified. The reactor monomer feed stream is pressurized to over the reaction pressure via a mechanical compressor. The solvent and comonomer feed streams are pressurized to over the reaction pressure via pumps. Individual catalyst components are manually batch-diluted in the purified solvent and pressurized to over the reaction pressure. All reaction feed streams are measured using mass flowmeters and independently controlled by a computer-automated valve control system.
[0239] Two reactor systems are used in a parallel configuration. Each continuous solution polymerization reactor consists of a liquid-filled, non-adiabatic, isothermal circulating loop reactor that replicates a continuous stirred tank reactor (CSTR) with heat removal. All fresh solvent, monomer, comonomer, hydrogen, and catalyst component feeds are independently controlled. The total fresh feed streams to each reactor (solvent, monomer, comonomer, and hydrogen) are temperature-controlled to maintain a single solution phase by passing the feed streams through a heat exchanger. The total fresh feed to each polymerization reactor is injected into the reactor at two locations, with approximately equal reactor volumes between each injection point. The fresh feed is controlled so that each injector accepts half of the total fresh feed flow rate. Catalyst components are injected into the polymerization reactors through specially designed injection needles. The main catalyst component feed is computer-controlled to maintain monomer conversion in each reactor at a specific target. Co-catalyst components are supplied based on a calculated specific molar ratio to the main catalyst component. Immediately after the injection point of each reactor feed, the feed stream is mixed with the contents of the circulating polymerization reactor using a static mixing element. The contents of each reactor are passed through a heat exchanger, which plays a role in removing most of the reaction heat, and the coolant side temperature plays a role in maintaining an isothermal reaction environment at a specific temperature, and the mixture is continuously circulated. Circulation around each reactor loop is provided by a pump.
[0240] The effluents from the first and second polymerization reactors are combined before any additional processing. This final combined reactor effluent enters a zone where the effluent is deactivated by the addition and reaction with a suitable reagent (water). At this same reactor outlet site, other additives are added for polymer stabilization (typical antioxidants suitable for stabilization during extrusion and inflation film production, such as octadecyl 3,5-di-Tert-butyl-4-hydroxyhydrocinnamate, tetrakis(methylene(3,5-di-Tert-butyl-4-hydroxyhydrocinnamate))methane, and tris(2,4-di-Tert-butyl-phenyl)phosphite).
[0241] Following catalyst deactivation and additive addition, the reactor effluent enters a devolving system where the polymer is removed from the non-polymer stream. The isolated polymer molten material is pelletized and collected. The non-polymer stream passes through various instruments that separate most of the ethylene removed from the system. Most of the solvent and unreacted comonomers are recycled back into the reactor after passing through a purification system. Small amounts of solvent and comonomers are purged from the process.
[0242] The reactor flow feed data flow corresponding to the values in Table 2A, used to generate the examples, is schematically illustrated in Figure 4. The data is presented to account for the complexity of the solvent recirculation system and to make the reaction system easier to handle as a through-flow diagram. Table 1B shows the catalyst referenced in Table 2A for Example 1A. [Table 3]
[0243] Example 2: Comparative compositions A-J Comparative compositions A to C were prepared by the methods described below herein. Comparative compositions D to F are bimodal polyethylene compositions generally prepared using the catalyst system and process provided for preparing the first composition of the invention in PCT Publication No. 2015 / 200743. Comparative compositions G to J are commercially available polyethylene compositions. Table 3 shows the commercially available polyethylene compositions of comparative compositions G to J. [Table 4]
[0244] The preparation of comparative compositions A to C is described as follows: Before introducing them into the reaction environment, all raw materials (monomers and comonomers) and the process solvent (high-purity isoparaffinic solvent with a narrow boiling point range, Isopar-E) are purified using molecular sieves. Hydrogen is supplied under pressure as high-purity grade and is not further purified. The reactor monomer feed stream is pressurized to over the reaction pressure via a mechanical compressor. The solvent and comonomer feed streams are pressurized to over the reaction pressure via pumps. Individual catalyst components are manually batch diluted with the purified solvent and pressurized to over the reaction pressure. All reaction feed streams are measured using mass flowmeters and independently controlled by a computer-automated valve control system.
[0245] Two reactor systems are used in a series configuration. Each continuous solution polymerization reactor consists of a liquid-filled, non-adiabatic, isothermal circulating loop reactor that replicates a continuous stirred tank reactor (CSTR) with heat removal. All fresh solvent, monomer, comonomer, hydrogen, and catalyst component feeds are independently controlled. The total fresh feed streams to each reactor (solvent, monomer, comonomer, and hydrogen) are temperature-controlled to maintain a single solution phase by passing the feed streams through a heat exchanger. The total fresh feed to each polymerization reactor is injected into the reactor at two locations, with approximately equal reactor volumes between each injection point. The fresh feed is controlled so that each injector accepts half of the total fresh feed flow rate. Catalyst components are injected into the polymerization reactors through injection needles. The main catalyst component feed is computer-controlled to maintain monomer conversion in each reactor at a specific target. Co-catalyst components are supplied based on a calculated specific molar ratio to the main catalyst component. Immediately after the injection point of each reactor feed, the feed stream is mixed with the contents of a circulating polymerization reactor having a static mixing element. The contents of each reactor are passed through a heat exchanger, which plays a role in removing most of the reaction heat, and the coolant side temperature plays a role in maintaining an isothermal reaction environment at a specific temperature, and are continuously circulated. Circulation around each reactor loop is provided by a pump.
[0246] In a double series reactor configuration, the effluent from the first polymerization reactor (containing solvent, monomer, comonomer, hydrogen, catalyst components, and polymer) exits the first reactor loop and is added to the second reactor loop.
[0247] The second reactor effluent enters a zone where the effluent is deactivated by the addition and reaction with a suitable reagent (water). At this same reactor outlet, other additives are added for polymer stabilization (typical antioxidants suitable for stabilization during extrusion and film production, such as octadecyl 3,5-di-Tert-butyl-4-hydroxyhydrocinnamate, tetrakis(methylene(3,5-di-Tert-butyl-4-hydroxyhydrocinnamate))methane, and tris(2,4-di-Tert-butyl-phenyl)phosphite).
[0248] Following catalyst deactivation and additive addition, the reactor effluent enters a devolving system where the polymer is removed from the non-polymer stream. The isolated polymer molten material is pelletized and collected. The non-polymer stream passes through various instruments that separate most of the ethylene removed from the system. Most of the solvent and unreacted comonomers are recycled back into the reactor after passing through a purification system. Small amounts of solvent and comonomers are purged from the process.
[0249] The reactor flow feed data flow corresponding to the values in Table 4A, used to generate the examples, is schematically illustrated in Figure 3. The data is presented to account for the complexity of the solvent recirculation system and to make the reaction system easier to handle as a through-flow diagram. Table 1B shows the catalysts and co-catalysts shown in Table 4A. [Table 5]
[0250] Example 3: Analysis of polyethylene samples Polyethylene compositions 1-6 of Examples 1A and 1B, comparative polyethylene compositions A-C of Example 2, and commercially available comparative polyethylene samples D-J of Example 2 were analyzed by iCCD. The iCCD data for polyethylene composition 5 is shown in Figure 2. Additional data generated from the iCCD tests of all samples are shown in Tables 5A and 5B. Specifically, Tables 5A and 5B include the analysis of iCCD data, including the area of the first and second polyethylene fractions (45-87°C and 95-120°C). Additional data for each example composition is also provided, including overall density, dart strength (Method A), melt index, and weight-average molecular weight of the second PE fraction. These properties are based on the single-layer inflation film obtained from each polyethylene sample.
[0251] To conduct darting tests and other tests based on the molded film, a 2-mil inflation film was molded using a polyethylene sample. Specifically, the single-layer inflation film was produced via an Egan Davis Standard extruder equipped with an ID 3.5-inch semi-grooved barrel, an L / D ratio of 30 / 1, a barrier screw, and an Alpine air ring. The extrusion line has an 8-inch die with internal bubble cooling. The extrusion line also has a film thickness gauge scanner. The film production conditions were as follows: film thickness maintained at 2 mils (0.001 in or 0.0254 mm), blow-up ratio (BUR) of 2.5, die gap of 70 mils, and frost line height (FLH) of 37 inches. The output speed was kept constant at 260 lbs / hour. [Table 6] [Table 7]
[0252] The results showed that all comparative compositions contained at least 0.924 g / cm³. 3 This demonstrates that the overall density does not show equivalent dirt intensity. For example, some comparative examples have high dirt intensity, but these samples have a much lower density. High-density comparative sample (e.g., 0.924 g / cm³) 3 ~0.936 g / cm³ 3 ) exhibits a much lower dirt intensity (e.g., less than 1000 grams).
[0253] Furthermore, some of the compositions in Example 1 had Dow rheology indices less than 10, such as 3.5, 4.6, and 5.5.
[0254] Example 4: Evaluation of the use of the disclosed polyethylene composition in the core layer Example 4 compares four multilayer film samples (films 4-1, 4-2, 4-3, and 4-4) prepared according to the embodiments disclosed and described herein with comparative multilayer film samples (comparison 4-A, comparison 4-B, comparison 4-C, comparison 4-D, comparison 4-E, comparison 4-F, comparison 4-G, and comparison 4-H). For all samples produced and tested in Example 4, the multilayer film had three layers, including two outer layers and one core layer. The material used for the outer layers was identical for each outer layer and remained constant throughout each sample. To observe the effect of using different materials in the core layer, each sample tested in Example 4 contained a core layer consisting of one material, although this material differed for each sample. In Example 4, samples with both an overall thickness of 55 μm and an overall thickness of 45 μm were produced to observe the down-gauge effect.
[0255] Films 4-1, 4-2, 4-3, and 4-4 are examples of multilayer films according to some embodiments of the present disclosure. As will be shown later in Table 6, polyethylene composition 1 (PE Comparative Example 1) prepared according to Example 1A was used in films 4-1 and 4-3, polyethylene composition 2 (PE Comparative Example 2) prepared according to Example 1A was used in films 4-2 and 4-4, and films 4-1, 4-2, 4-3, and 4-4 each contained DOWLEX® GM 8051 polyethylene (melt index: 2.16 kg and 0.9 g / 10 min at 190°C, density: 0.921 g / cm³). 3 (Available commercially from The Dow Chemical Company).
[0256] As will be shown later in Table 6, comparisons 4-A, 4-B, 4-C, 4-D, 4-E, 4-F, 4-G, and 4-H contain two or more DOWLEX® GM 8051 polyethylene (melt index: 2.16 kg and 0.9 g / 10 min at 190°C, density: 0.921 g / cm³). 3(Available commercially from The Dow Chemical Company), DOWLEX® 2049 polyethylene (melt index: 2.16 kg and 1.0 g / 10 min at 190°C, density: 0.926 g / cm³) 3 (Available commercially from The Dow Chemical Company), 6D20 polypropylene resin (melt index: 2.16 kg and 1.9 g / 10 min at 230°C, density: 0.900 g / cm³) 3 (commercially available from Braskem, "rPP"), as well as two bimodal polyethylene compositions (melt index: 2.16 kg and 0.85 g / 10 min at 190°C, density: 0.918 g / cm³). 3 ("Bimodal PE1") and (Melt index: 2.16 kg and 0.85 g / 10 min at 190°C, density: 0.926 g / cm³) 3 This included "bimodal PE2". Bimodal PE1 and bimodal PE2 are polyethylene compositions prepared using the catalyst system and process provided in PCT Publication No. 2015 / 200743 for preparing the first composition of the invention.
[0257] To produce the sample film of Example 4, the materials listed in Table 6 were formed into an inflation film on a 5-layer extrusion line with a blow-up ratio (BUR) of 2.5, a die temperature of 230°C, a die gap of 1.8 mm, a melting temperature of 225°C, and a rate of 12.5 kg / hour.
[0258] The structure and layer distribution of the multilayer film of Example 4 are provided in Table 6 as follows. [Table 8]
[0259] The specific properties of the multilayer film of Example 4 were measured according to the test methods disclosed herein, and these properties are provided in Table 7. [Table 9]
[0260] As shown in Table 7, for films with an overall thickness of 55 μm, Comparison 4-A showed the lowest secant coefficient among all the samples tested. Comparison 4-D showed a secant coefficient of 448 MPa but a dart B of less than 300 g. Comparisons 4-B, 4-C, and film 4-1 showed relatively similar secant coefficient characteristics. However, film 4-1 showed a higher dart B than comparisons 4-B and 4-C. Film 4-2 showed the highest dart B and secant coefficient values among all the samples tested in Example 4 with an overall thickness of 55 μm.
[0261] As shown in Table 7, for films with an overall thickness of 45 μm, comparison 4-E showed the second lowest secant coefficient among all the samples tested. Comparison 4-H showed a secant coefficient of 493 MPa but exhibited a dart B of less than 300 g. Comparisons 4-F, 4-G, and film 4-3 showed relatively similar secant coefficient characteristics. However, film 4-3 showed a higher dart B than comparisons 4-F and 4-G. Film 4-4, with an overall thickness of 45 microns, showed the highest dart B among all the samples tested in Example 4, and the highest secant coefficient among all samples with a polyethylene core and an overall thickness of 45 microns.
[0262] Accordingly, the results in Table 7 demonstrate that embodiments of the disclosure, including a core layer incorporating the polyethylene composition described herein, can provide unexpectedly superior dirt impact resistance compared to multilayer films including a core layer containing other polyolefins. Here, a balance between stiffness (secant coefficient of 2%) and dirt impact resistance can be observed in the multilayer film, which was not achieved by the comparative multilayer film. This balance between stiffness and toughness may be advantageous in various packaging applications, particularly when lower gauges are used (down gauge).
[0263] Example 5: Evaluation of the use of the disclosed polyethylene composition in the core layer and outer layer Example 5 compares three multilayer film samples prepared according to some embodiments described herein (films 5-1, 5-2, and 5-3) with comparative multilayer film samples (comparison 5-A, comparison 5-B, comparison 5-C, and comparison 5-D). For all samples produced and tested in Example 5, the multilayer films had three layers, including two outer layers and one core layer. In the outer layers of all samples tested in Example 5, the LDPE material used and the weight percentage of LDPE material in the outer layer remained constant. In the core layers of all samples tested in Example 5, the masterbatch material, the amount of masterbatch material, and the HDPE material used in the core layer remained constant. In Example 5, samples with an overall thickness of 4.0 mil (101.6 μm) and an overall thickness of 4.23 mil (107.4 μm) were produced to observe the effect of downgauging on specific properties. To observe the effect of using the disclosed polyethylene composition in the core and outer layers, the balance of materials in the outer and core layers was varied for the sample in Example 5.
[0264] Films 5-1, 5-2, and 5-3 are examples of multilayer films according to some embodiments described herein. As shown later in Table 8, polyethylene composition 4 (PE Comparative Example 4) prepared according to Example 1A was used in film 5-1, polyethylene composition 2 prepared according to Example 1A was used in films 5-2 and 5-3, and AGILITY® 1200 polyethylene (melt index: 2.16 kg and 0.25 g / 10 min at 190°C, density: 0.919 g / cm³) was used. 3 (Commercially available from The Dow Chemical Company) is used in films 5-1, 5-2, and 5-3, and is DMDH 6400 polyethylene (melt index: 2.16 kg and 0.80 g / 10 min at 190°C, density: 0.961 g / cm³). 3(Commercially available from The Dow Chemical Company) was used in films 5-1, 5-2, and 5-3, and masterbatch TiO2 (commercially available from Ampacet Corporation) was used in films 5-1, 5-2, and 5-3.
[0265] As will be shown later in Table 8, comparisons 5A to 5D are EXCEED (trademark) 1018 polyethylene (melt index: 2.16 kg and 1.0 g / 10 min at 190°C, density: 0.918 g / cm³). 3 (Available commercially from ExxonMobil), AGILITY® 1200 polyethylene (melt index: 2.16 kg and 0.25 g / 10 min at 190°C, density: 0.919 g / cm³) 3 (Commercially available from The Dow Chemical Company), DMDH 6400 polyethylene (melt index: 2.16 kg and 0.80 g / 10 min at 190°C, density: 0.961 g / cm³) 3 It was formed from bimodal PE1, bimodal PE2 (commercially available from The Dow Chemical Company), and masterbatch TiO2 (commercially available from Ampacet Corporation).
[0266] To produce the sample film of Example 5, the materials listed in Table 8 were formed into film on an Alpine 7-layer inflation film line. The extruder size was 2.5 inches, the die diameter was 7.87 inches, the die gap was 78.7 mils, the blow-up ratio (BUR) was 1.75, the melting temperature was 458°F to 472°F, the output speed was 250 lbs / hour, the line speed was 56 ft. / min (3-layer co-extrusion), and the frost line height (FLH) was 36 inches.
[0267] The structure and layer distribution of the multilayer film of Example 5 are provided in Table 8 as follows. [Table 10]
[0268] The properties of the multilayer film of Example 5 were measured according to the test methods disclosed herein, and these properties are provided in Table 9. [Table 11]
[0269] As shown in Table 9, film 5-3 exhibited the highest dirt resistance, followed by films 5-1 and 5-2. Furthermore, film 5-1 exhibited the lowest tensile creep properties, followed by film 5-2, comparative 5-A, and film 5-3. Thus, the results in Table 9 demonstrate that such embodiments described herein, including a core layer incorporating the polyethylene composition described herein, can provide unexpectedly superior dirt impact resistance and tensile creep properties compared to multilayer films including a core layer containing other polyolefins.
[0270] Example 6: Evaluation of the use of the disclosed polyethylene composition in the core layer to reduce or eliminate the need for polyamide. Example 6 compares two multilayer film samples prepared according to some embodiments described herein (films 6-1 and 6-2) with comparative multilayer film samples (comparisons 6-A, 6-B, 6-C, and 6-D). For all samples produced and tested in Example 6, the multilayer films had three layers, including two outer layers and one core layer. In the outer layers of all samples tested in Example 6, the LDPE material used, the weight percentage of LDPE material in the outer layer, the HDPE material used, and the weight percentage of HDPE material in the outer layer remained constant. To observe the effect of utilizing the disclosed polyethylene composition in the core and outer layers, the polyethylene to HDPE ratio in the core layer was varied across each sample in an attempt to maintain a similar film density.
[0271] To produce the film of Example 6, the amounts of material listed in Tables 10 and 11 were formed into an inflation film on a 7-layer Alpine co-extrusion blow line. The parameters of the inflation film line included a die of 9.84 mils, a die gap of 78.7 mils, a BUR of 2.5:1, a speed of 350 lbs / hour, a die temperature of approximately 450°F, a melting temperature of 439°F to 497°F (depending on the material being extruded), and an actual speed of 11.3 lbs / hour / in.
[0272] As shown in Table 10, reference structures containing polyamide (nylon) were generated. The materials used to generate Comparative 6-A included bimodal PE1, ELITE™ 5960 polyethylene (melt index: 2.16 kg and 0.85 g / 10 min at 190°C, density: 0.962 g / cm³). 3 (Available commercially from The Dow Chemical Company), as well as DOW LDPE 132I (melt index: 2.16 kg and 0.25 g / 10 min at 190°C, density: 0.921 g / cm³). 3 (Commercially available from The Dow Chemical Company), Bynel 41E710 anhydrous modified LLDPE resin (melt index: 2.16 kg and 1.2 g / 10 min at 190°C, density: 0.862 g / cm³) 3 This includes (commercially available from The Dow Chemical Company) and Ultramid C40L polyamide (commercially available from BASF).
[0273] Table 10 shows the structure and layer distribution of Comparison 6-A. [Table 12]
[0274] Films 6-1 and 6-2 are examples of multilayer films according to some embodiments described herein. As shown later in Table 11, polyethylene composition 2 (PE Comparative Example 2), prepared according to Example 1A, was used in film 6-1, and polyethylene composition 3 (PE Comparative Example 3), prepared according to Example 1A, was used in film 6-2. Films 6-1 and 6-2 contain bimodal PE1, ELITE® 5960 polyethylene (melt index: 2.16 kg and 0.85 g / 10 min at 190°C, density: 0.962 g / cm³). 3 (Commercially available from The Dow Chemical Company), DOW LDPE 132I (Melt index: 2.16 kg and 0.25 g / 10 min at 190°C, Density: 0.921 g / cm³) 3 (Commercially available from The Dow Chemical Company), and two polyethylene compositions (melt index: 2.16 kg and 0.85 g / 10 min at 190°C, density: 0.925 g / cm³). 3 This also includes "bimodal PE3". Bimodal PE3 is generally a polyethylene composition prepared using the catalyst system and process provided for preparing the first composition in PCT Publication No. 2015 / 200743.
[0275] Furthermore, as will be shown later in Table 11, in comparisons 6-B, 6-C, and 6-D, bimodal PE1 (melt index: 2.16 kg and 0.85 g / 10 min at 190°C, density: 0.918 g / cm³) 3 (Available commercially from The Dow Chemical Company), ELITE® 5960 polyethylene (melt index: 2.16 kg and 0.85 g / 10 min at 190°C, density: 0.962 g / cm³) 3 (Commercially available from The Dow Chemical Company), DOW LDPE 132I (Melt index: 2.16 kg and 0.25 g / 10 min at 190°C, Density: 0.921 g / cm³) 3(Available commercially from The Dow Chemical Company), as well as comparative composition C of Example 2 ("Comparative Example C of Example 2"), were used.
[0276] The structure of the film produced in Example 6 is shown below. [Table 13]
[0277] The properties of the multilayer film of Example 6 were measured according to the test methods disclosed herein, and these properties are provided in Table 12. [Table 14]
[0278] As shown in Table 12, film 6-1 exhibited the highest dirt resistance, followed by comparative 6-A and film 6-2. Furthermore, film 6-2 exhibited the highest coefficient, followed by film 6-1, and comparative 6-A exhibited the lowest coefficient. Thus, the results in Table 12 demonstrate that such embodiments described herein, incorporating the polyethylene compositions described herein and including a core layer without a polyamide core layer, can offer an unexpected balance of superior dirt impact resistance and tensile creep properties compared to multilayer films including a core layer containing other polyolefins or polyamides.
[0279] It will be apparent that modifications and changes are possible without departing from the scope of this disclosure as defined in the attached claims. More specifically, while certain aspects of this disclosure are identified herein as preferred or particularly advantageous, this disclosure is intended not to be limited to these aspects.
Claims
1. A multilayer film, comprising: A first layer, 1. A polyethylene composition comprising: (a) a first polyethylene fraction having a single peak in a temperature range of 45°C to 87°C in an elution profile by improved comonomer composition distribution (iCCD) analysis, wherein a first polyethylene fraction area is the area in the elution profile under the single peak of the first polyethylene fraction at 45°C to 87°C; (b) a second polyethylene fraction having a single peak in the temperature range of 95°C to 120°C in an elution profile measured by the iCCD analysis method, wherein a second polyethylene fraction area is an area in the elution profile under the single peak of the second polyethylene fraction at 95°C to 120°C; The polyethylene composition has a viscosity of 0.924 g / cm 3 ~0.936g / cm 3 and a melt index (I 2 a first layer comprising a polyethylene composition having a first polyethylene fraction area constituting at least 40% of the total area of the elution profile, a ratio of the first polyethylene fraction area to the second polyethylene fraction area being 0.75 to 2.25, and a width of the single peak of the second polyethylene fraction at 50 percent of the peak height being less than 5.0° C.; a second layer comprising the first polyolefin; a third layer comprising a second polyolefin; and Including, the first layer is disposed between the second layer and the third layer; A multi-layer film, wherein the first polyolefin and the second polyolefin are the same or different.
2. The first polyolefin composition, the second polyolefin composition, or both, have a viscosity of 0.870 g / cm 3 ~0.970g / cm 3 10. The multilayer film of claim 1, comprising a polyethylene having a density of
3. the first layer is in direct contact with the second layer and the third layer; The multilayer film of claim 1 or 2, wherein the second layer and the third layer are outermost layers of the multilayer film.
4. 0.924 g / cm 3 ~0.936g / cm 3 and a ratio of weight average molecular weight to number average molecular weight (M w / M n The multilayer film according to any one of claims 1 to 3, having a molecular weight distribution, expressed as a function of molecular weight (Mw / Mn), in the range of 2.5 to 8.
0.
5. The multilayer film of any one of claims 1 to 4, wherein the multilayer film has a thickness of less than 500 micrometers (μm).
6. The first layer has a toughness of 0.940 g / cm as measured in accordance with ASTM 742. 3 The multilayer film of any one of claims 1 to 5, further comprising a polyethylene having a density greater than
7. A multilayer film, comprising: a first layer, comprising 10% to 80% by weight of the total weight of the multilayer film, the first layer comprising:
1. A polyethylene composition comprising: (a) a first polyethylene fraction having a single peak in a temperature range of 45°C to 87°C in an elution profile by improved comonomer composition distribution (iCCD) analysis, wherein a first polyethylene fraction area is the area in the elution profile under the single peak of the first polyethylene fraction at 45°C to 87°C; (b) a second polyethylene fraction having a single peak in the temperature range of 95°C to 120°C in an elution profile measured by the iCCD analysis method, wherein a second polyethylene fraction area is an area in the elution profile under the single peak of the second polyethylene fraction at 95°C to 120°C; The polyethylene composition has a viscosity of 0.924 g / cm 3 ~0.936g / cm 3 and a melt index (I 2 a first layer comprising a polyethylene composition having a first polyethylene fraction area constituting at least 40% of the total area of the elution profile, a ratio of the first polyethylene fraction area to the second polyethylene fraction area being 0.75 to 2.25, and a width of the single peak of the second polyethylene fraction at 50 percent of the peak height being less than 5.0° C.; 0.910 g / cm 3 ~0.936g / cm 3 a second layer comprising a first linear low density polyethylene having a density of 0.910 g / cm 3 ~0.936g / cm 3 a third layer comprising a second linear low density polyethylene having a density of Including, the first layer is disposed between the second layer and the third layer; A multilayer film, wherein the first linear low density polyethylene and the second linear low density polyethylene are the same or different.
8. 8. The multilayer film of claim 7, wherein the multilayer film has a dart drop impact of at least 400 grams as measured according to ASTM D1709 Method B.
9. 9. The multilayer film of claim 7 or 8, wherein the multilayer film has an average secant modulus in the machine direction of from 29,000 psi to 37,000 psi, the average secant modulus being measured according to ASTM D882.
10. A multilayer film, comprising: A first layer, 0.940 g / cm when measured according to ASTM 742 3 ~0.970g / cm 3 a high density polyethylene composition having a density of 1. A polyethylene composition comprising: (a) a first polyethylene fraction having a single peak in a temperature range of 45°C to 87°C in an elution profile by improved comonomer composition distribution (iCCD) analysis, wherein a first polyethylene fraction area is the area in the elution profile under the single peak of the first polyethylene fraction at 45°C to 87°C; (b) a second polyethylene fraction having a single peak in the temperature range of 95°C to 120°C in an elution profile measured by the iCCD analysis method, wherein a second polyethylene fraction area is an area in the elution profile under the single peak of the second polyethylene fraction at 95°C to 120°C; The polyethylene composition has a viscosity of 0.924 g / cm 3 ~0.936g / cm 3 and a melt index (I 2 a polyethylene composition having a first polyethylene fraction area constituting at least 40% of the total area of the elution profile, a ratio of the first polyethylene fraction area to the second polyethylene fraction area being 0.75 to 2.25, and a width of the single peak of the second polyethylene fraction at 50 percent of the peak height being less than 5.0° C.; A second layer comprising at least 50 wt. % of a first linear low density polyethylene based on the total weight of the second layer, the first linear low density polyethylene having a viscosity of 0.910 g / cm 3 ~0.936g / cm 3 a second layer having a density of A third layer comprising at least 50 wt. % of a second linear low density polyethylene based on the total weight of the third layer, the second linear low density polyethylene having a viscosity of 0.910 g / cm 3 ~0.936g / cm 3 a third layer having a density of Including, the first layer is disposed between the second layer and the third layer; A multilayer film, wherein the first linear low density polyethylene and the second linear low density polyethylene are the same or different.
11. 11. The multilayer film of claim 10, wherein the multilayer film has a cross-direction tensile creep of less than 50% at 1.4 kg / 50° C. / 5 hrs as measured according to ASTM 2990.
12. 12. The multilayer film of claim 10 or 11, wherein the multilayer film has a dart drop impact of at least 600 grams as measured according to ASTM D1709 Method B.
13. A multilayer film, comprising: A first layer, 0.940 g / cm 3 ~0.970g / cm 3 a first polyethylene having a density of 0.924 g / cm 3 ~0.936g / cm 3 a first layer comprising a first polyethylene composition having a density of A second layer, 0.940 g / cm 3 ~0.970g / cm 3 a second polyethylene having a density of 0.916 g / cm 3 ~0.935g / cm 3 a first low density polyethylene having a density of 0.924 g / cm 3 ~0.936g / cm 3 a second layer comprising a second polyethylene composition having a density of A third layer, 0.916 g / cm 3 ~0.935g / cm 3 a second low density polyethylene having a density of 0.924 g / cm 3 ~0.936g / cm 3 a third layer comprising a third polyethylene composition having a density of Including, the first layer is disposed between the second layer and the third layer; the first polyethylene and the second polyethylene are the same or different; the first low density polyethylene and the second low density polyethylene are the same or different; The first polyethylene composition, the second polyethylene composition, and the third polyethylene composition are the same or different compositions, each comprising: (a) a first polyethylene fraction having a single peak in a temperature range of 45°C to 87°C in an elution profile by improved comonomer composition distribution (iCCD) analysis, wherein a first polyethylene fraction area is the area in the elution profile under the single peak of the first polyethylene fraction at 45°C to 87°C; (b) a second polyethylene fraction having a single peak in the temperature range of 95°C to 120°C in an elution profile measured by the iCCD analysis method, wherein a second polyethylene fraction area is an area in the elution profile under the single peak of the second polyethylene fraction at 95°C to 120°C; The polyethylene composition has a viscosity of 0.924 g / cm 3 ~0.936g / cm 3 and a melt index (I 2 ), wherein the first polyethylene fraction area constitutes at least 40% of the total area of the elution profile, the ratio of the first polyethylene fraction area to the second polyethylene fraction area is from 0.75 to 2.25, and the width of the single peak of the second polyethylene fraction at 50 percent of the peak height is less than 5.0° C.
14. 14. The multilayer film of claim 13, wherein the multilayer film has a dart drop impact of at least 350 grams as measured according to ASTM D1709 Method B.
15. 15. The multilayer film of claim 13 or 14, wherein the multilayer film has an average secant modulus in the machine direction greater than 50,000 psi, the average secant modulus being measured according to ASTM D882.